Laminated body including transparent high heat-resistant film
By optimizing the laminated structure and interface intermixing thickness in the laminated body of the transparent high heat-resistant film and the inorganic substrate, the problems of poor productivity and difficulty in peeling of the equipment connector in the prior art are solved, and a transparent high heat-resistant film equipment connector that is efficient and easy to manufacture is realized.
Patent Information
- Application Number
- CN202180034225.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-09
- Filing Date
- 2021-05-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-05-25
AI Technical Summary
In the prior art, equipment connectors for manufacturing transparent high heat-resistant films have poor productivity, especially when large-area laser processing requires a high degree of accuracy, and stains are prone to occur and equipment failures. Meanwhile, the conventional laminated body is difficult to mechanically peel off after forming a device on the polyimide film layer.
A layered body of a transparent high heat-resistant film without adhesive and an inorganic substrate is used to optimize the laminate structure and inter-mix thickness of the laminate structure and interface, so as to achieve easy peelability and high heat resistance of the film. Specific measures include using a layered transparent high heat-resistant film with more than two layers. The CTE in which the first transparent high heat-resistant film layer contacts the inorganic substrate is preferably 20 ppm/K or less. The CTE in the second transparent high heat-resistant film layer is preferably matched with the first layer to reduce the difference in CTE and improve the peel strength.
The easy peelability of transparent high heat-resistant film and inorganic substrate is achieved, which simplifies the manufacturing process of the equipment, improves production efficiency, and reduces the possibility of equipment failure.
Smart Images

Figure CN115551713B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate containing a transparent high heat-resistant film. Background Art
[0002] In recent years, there has been an increasing demand for flexible and stretchable sheets that can be mounted with multiple devices at intervals. Such sheets can be used, for example, on curved surfaces such as the body. In addition, they can also be used on electronic components with bends and reelable electronic components. If these sheets are transparent, they are expected to have a variety of uses centered on display applications, and therefore have been subject to much research.
[0003] Patent document 1 discloses a method for manufacturing a polyimide film for a supporting substrate used in manufacturing an organic EL device that is thin / lightweight / flexible, has no cracking and peeling problems caused by thermal stress, and has excellent dimensional stability. The method comprises coating a resin solution of polyimide or a polyimide precursor on a base substrate so that the thickness of the polyimide film is 50 μm or less, performing a heat treatment, forming a polyimide film on the base substrate, and separating the polyimide film from the base substrate. The transmittance of the polyimide film in the wavelength region of 440 nm to 780 nm is 80% or more, and the transmittance at 400 nm is 80% or less. In order to separate the polyimide film from the base substrate, a laser is irradiated on the bottom surface of the polyimide film through the base substrate to manufacture a polyimide film for a supporting substrate of a display device.
[0004] In addition, in Patent Document 2, as a laminate having a silane coupling layer between an inorganic layer and a polyimide film layer, a laminate having excellent heat resistance and insulation properties formed by laminating a polyimide film having a higher level of heat resistance and flexibility and an inorganic layer selected from a glass plate, a ceramic plate, a silicon wafer, and a metal is extremely meaningful when used in the manufacture of electronic components, optical functional parts, electronic parts, etc.
[0005] Prior art literature
[0006] Patent Literature
[0007] [Patent Document 1] Japanese Patent Application Publication No. 2018-132768
[0008] [Patent Document 2] Japanese Patent No. 5304490 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, in the manufacturing method of the circuit substrate described in Patent Document 1, it is necessary to irradiate the bottom and front surfaces of the polyimide film with laser through the base substrate, which has poor productivity. In particular, laser processing requires a high degree of precision when the area is large, which makes mass production difficult. In addition, since smears are generated during laser processing, these smears will become particles and cause equipment failures, which will also cause wiring disconnection. In addition, the laminate described in Patent Document 2 has a 180-degree peel strength of more than 1N / cm between the inorganic layer and the polyimide film, and it is difficult to mechanically peel off the polyimide film on which the device is formed after forming the device on the polyimide film layer.
[0011] The present invention is made in view of the above problems, and its purpose is to provide a method for manufacturing a device connection body that can be mass-produced, after forming a device on a transparent high heat-resistant film, the transparent high heat-resistant film and the inorganic substrate can be easily peeled off, so that a film with electronic components can be easily manufactured. In addition, the present invention provides a laminate of a transparent high heat-resistant film and an inorganic substrate for manufacturing the device.
[0012] The inventors of the present invention have conducted in-depth research on the manufacture of devices on transparent high heat-resistant films. As a result, it was found that if the following structure is used, the device can be easily manufactured on the transparent high heat-resistant film and can be mass-produced, thereby realizing the present invention. That is, the laminated body involved in the present invention is composed of the following structure.
[0013] A laminated body comprising a transparent high heat-resistant film and an inorganic substrate, which laminated body is substantially free of adhesive.
[0014] The peel strength between the transparent high heat-resistant film and the inorganic substrate is 0.3 N / cm or less, and the CTE of the transparent high heat-resistant film is 50 ppm / K or less.
[0015] The transparent high heat-resistant film has a stacked structure of more than two layers, and the intermixing thickness of the interface between the first transparent high heat-resistant film layer in contact with the inorganic substrate and the second transparent high heat-resistant film layer adjacent to the first transparent high heat-resistant film layer but not in contact with the inorganic substrate is preferably less than 800 nm.
[0016] The transparent high heat-resistant film has a laminated structure of two or more layers, and the CTE of the first transparent high heat-resistant film layer in contact with the inorganic substrate is preferably 20 ppm / K or less.
[0017] The transparent high heat-resistant film has a laminated structure of two or more layers, and the first transparent high heat-resistant film layer in contact with the inorganic substrate is preferably a transparent polyimide.
[0018] The transparent high heat-resistant film has a laminated structure of two or more layers, and at least one layer of the second transparent high heat-resistant film layer not in contact with the inorganic substrate is preferably a transparent polyimide.
[0019] The transparent high heat-resistant film has a laminated structure of two or more layers, and the first transparent high heat-resistant film layer in contact with the inorganic substrate preferably includes the structure of Formula 1 and / or the structure of Formula 2.
[0020]
Chemistry 1
[0021]
[0022]
Chemistry 2
[0023]
[0024] The long side of the inorganic substrate is preferably 300 mm or longer.
[0025] A method for manufacturing a film with electronic components comprises forming electronic components on a transparent high heat-resistant film of a laminate and then peeling the film off from an inorganic substrate.
[0026] Effects of the Invention
[0027] According to the present invention, a method for manufacturing a device connector can be provided, which can easily manufacture a film with electronic components and can be mass-produced because the transparent high heat-resistant film and the inorganic substrate can be easily peeled off after the device is formed. In addition, a laminate of the transparent high heat-resistant film and the inorganic substrate can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0028]
Figure 1
[0029]
Figure 2
[0030]
Figure 3
[0031]
Figure 4
[0032] Explanation of symbols
[0033] 1 Flow meter
[0034] 2 Gas inlet
[0035] 3 Chemical liquid tank (silane coupling agent tank)
[0036] 4 Warm water tank (water bath heating)
[0037] 5. Heater
[0038] 6 Processing room (chamber)
[0039] 7. Substrate
[0040] 8 Exhaust port
[0041] 11. 1st transparent high heat resistant film layer
[0042] 12 Second transparent high heat resistant film layer
[0043] 13 Silane coupling agent layer
[0044] 14 Inorganic substrate
[0045] 15 Electronic components
[0046] 16 Membrane with electronic components
[0047] 17 Laminated body
[0048] 18 decks DETAILED DESCRIPTION
[0049] Hereinafter, embodiments of the present invention will be described.
[0050] <Transparent high heat-resistant film>
[0051] The transparent high heat-resistant film in this specification is preferably a film with a melting point of 250°C or more, more preferably 300°C or more, and further preferably 400°C or more. In addition, it is preferably a film made of a polymer having a glass transition temperature of 200°C or more, more preferably 320°C or more, and further preferably 380°C or more. Hereinafter, in order to avoid complexity, it is referred to as a polymer. In this specification, the melting point and the glass transition temperature are obtained by differential calorimetry analysis (DSC). It should be noted that when the melting point is greater than 500°C, the thermal deformation behavior when heated at this temperature can be visually observed to determine whether the melting point has been reached.
[0052] In addition, as for transparency, a total light transmittance of 75% or more is preferred. It is more preferably 80% or more, further preferably 85% or more, further preferably 87% or more, and particularly preferably 88% or more. The upper limit of the total light transmittance of the transparent high heat-resistant film is not particularly limited, but in order to be used as a film with electronic components (hereinafter also referred to as flexible electronic components), it is preferably 98% or less, and more preferably 97% or less.
[0053] Examples of the transparent high heat-resistant film (hereinafter also referred to as polymer film) include polyimide resins such as polyimide, polyamideimide, polyetherimide, and fluorinated polyimide (for example, aromatic polyimide resins and alicyclic polyimide resins); copolyesters such as polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, and polyethylene 2,6-naphthalate (for example, wholly aromatic polyesters and semi-aromatic polyesters); copoly(meth)acrylates represented by polymethyl methacrylate; polycarbonate; polyamide; polysulfone; polyethersulfone; polyetherketone; cellulose acetate; cellulose nitrate; aromatic polyamide; polyvinyl chloride; polyphenol; polyarylate; polyacetal; modified polyphenylene ether; polyphenylene sulfide; polyphenylene ether; polystyrene; polybenzoxazole; polybenzothiazole; polybenzimidazole; cyclic polyolefin; liquid crystal polymer films. In addition, those reinforced with glass fillers, glass fibers, etc. can also be exemplified.
[0054] However, since the polymer film is based on the process of being used with a heat treatment at 250° C. or higher, the polymer films that can be actually used are limited. The polymer film is preferably a film made of so-called super engineering plastics, and more specifically, aromatic polyimide films, alicyclic polyimide films, aromatic amide films, aromatic amideimide films, amideimide films, aromatic benzoxazole films, aromatic benzothiazole films, aromatic benzimidazole films, cyclic polyolefins, liquid crystal polymers, etc. can be cited.
[0055] The following is a detailed description of a polyimide resin film (sometimes also referred to as a polyimide film) of an example of the polymer film. Usually, the polyimide resin film is obtained by reacting a polyamic acid (polyimide precursor) solution obtained by diamines and tetracarboxylic acids in a solvent, coating it on a support for making a polyimide film, and drying it to form a green film (hereinafter referred to as "precursor film" or "polyamic acid film"), and further the polyimide film is made by heat treating the green film at high temperature under a support or peeling off from the support to obtain a dehydration ring-closure reaction. Here, the green film refers to a film of a polyamic acid containing a solvent and having self-supporting properties. The solvent content of the green film is not particularly limited as long as it has self-supporting properties, preferably 1% by mass or more, more preferably 5% by mass or more, more preferably 10% by mass or more, more preferably 20% by mass or more, and particularly preferably 30% by mass or more. In addition, it is preferably 80% by mass or less, more preferably 70% by mass or less, more preferably 60% by mass or less, and particularly preferably 50% by mass or less.
[0056] The coating of polyamic acid (polyimide precursor) solution, for example, can suitably use currently known solution coating means such as spin coating, scraping, applicator (applicator), comma coater, screen printing method, slit coating, reverse coating, dip coating, curtain coating, slit die coating.Because the width of material selection in the method for coating polyamic acid solution to make film is wider, it is easy to find the preferred material that is easy to peel off and therefore easy to study, must control imidization reaction on the other hand.In contrast, the film making of the film of imidization reaction is not accompanied, owing to having the advantage that film making is easy, so must suitably use accordingly.
[0057] The polyimide film in the present invention is a polymer film having an imide bond in the main chain, preferably a polyimide film or a polyamideimide film, more preferably a polyimide film. In addition, a polyamide film is also preferred.
[0058] Usually, the polyimide film is obtained by, as described above, applying a polyamic acid (polyimide precursor) solution obtained by reacting diamines and tetracarboxylic acids in a solvent to a support for the production of the polyimide film, drying to form a raw film, and further heat-treating the raw film at high temperature for dehydration ring-closure reaction on the support for the production of the polyimide film or in a state in which the raw film is peeled off from the support. In addition, as another method, a polyimide solution obtained by dehydration ring-closure reaction of diamines and tetracarboxylic acids in a solvent is applied to a support for the production of the polyimide film, dried to form a polyimide film containing, for example, 1 to 50% by mass of a solvent, and further treating the polyimide film containing 1 to 50% by mass of a solvent at high temperature on the support for the production of the polyimide film or in a state in which the polyimide film is peeled off from the support to dry it.
[0059] Typically, a polyamideimide film is prepared by coating a polyamideimide solution obtained by reacting a diisocyanate and a tricarboxylic acid in a solvent onto a support for the production of the polyamideimide film, drying the solution to form a polyamideimide film containing, for example, 1 to 50% by weight of the solvent, and further subjecting the polyamideimide film containing 1 to 50% by weight of the solvent to high temperature treatment on the support for the production of the polyamideimide or in a state peeled off from the support to dry the film.
[0060] In addition, usually, the polyamide film is obtained by coating a polyamide solution obtained by reacting diamines and carboxylic acids in a solvent on a support for polyamide film production, drying to form a polyamide film containing, for example, 1 to 50% by weight of the solvent, and further drying the polyamide film containing 1 to 50% by weight of the solvent at a high temperature on the support for polyamide production or in a state of being peeled off from the support.
[0061] As the tetracarboxylic acids, tricarboxylic acids, and dicarboxylic acids, aromatic tetracarboxylic acids (including anhydrides thereof), aliphatic tetracarboxylic acids (including anhydrides thereof), alicyclic tetracarboxylic acids (including anhydrides thereof), aromatic tricarboxylic acids (including anhydrides thereof), aliphatic tricarboxylic acids (including anhydrides thereof), alicyclic tricarboxylic acids (including anhydrides thereof), aromatic dicarboxylic acids, aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, etc., which are commonly used in polyimide synthesis, polyamideimide synthesis, and polyamide synthesis, can be used. Among them, aromatic tetracarboxylic anhydrides and aliphatic tetracarboxylic anhydrides are preferred, and aromatic tetracarboxylic anhydrides are more preferred from the viewpoint of heat resistance, and alicyclic tetracarboxylic acids are more preferred from the viewpoint of light transmittance. When tetracarboxylic acids are anhydrides, the anhydride structure in the molecule can be one or two, and preferably a thing (dianhydride) having two anhydride structures is used. Tetracarboxylic acids, tricarboxylic acids, and dicarboxylic acids can be used alone, or two or more can be used in combination.
[0062] In order to obtain a colorless and highly transparent polyimide in the present invention, examples of aromatic tetracarboxylic acids include 4,4'-(2,2-hexafluoroisopropylidene)diphthalic acid, 4,4'-oxydiphthalic acid, bis(1,3-dioxy-1,3-dihydro-2-benzofuran-5-carboxylic acid)1,4-phenylene, bis(1,3-dioxy-1,3-dihydro-2-benzofuran-5-yl)benzene-1,4-dicarboxylate, 4,4'-[4,4'-(3-oxy-1,3-dihydro-2-benzofuran-1,1-diyl)bis(benzene-1,4-diyloxy)]diphenyl-1,2-dicarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 4,4'-[(3-oxy-1,3-dihydro-2-benzofuran-1,1-diyl)bis(benzene-1,4-diyloxy)] -2-benzofuran-1,1-diyl)bis(toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[(3-oxylylidene-1,3-dihydro-2-benzofuran-1,1-diyl)bis(1,4-xylene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3-oxylylidene-1,3-dihydro-2-benzofuran-1,1-diyl)bis(4-isopropyl-toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3-oxylylidene-1,3-dihydro-2-benzofuran-1,1-diyl)bis(naphthalene-1,4-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3-oxylylidene-1,3-dihydro-2-benzofuran-1,1-diyl)bis(naphthalene-1,4-diyloxy)]dibenzene-1,2-dicarboxylic acid, '-(3H-2,1-benzoxathiol-1,1-dioxide-3,3-diyl)bis(benzene-1,4-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-benzophenonetetracarboxylic acid, 4,4'-[(3H-2,1-benzoxathiol-1,1-dioxide-3,3-diyl)bis(toluene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[(3H-2,1-benzoxathiol-1,1-dioxide-3,3-diyl)bis(1,4-xylene-2,5-diyloxy)]dibenzene-1,2-dicarboxylic acid, 4,4'-[4,4'-(3H-2,1-benzoxathiol-1,1 -dioxide-3,3-diyl)bis(4-isopropyl-toluene-2,5-diyloxy)]diphenyl-1,2-dicarboxylic acid, 4,4'-[4,4'-(3H-2,1-benzothiolane-1,1-dioxide-3,3-diyl)bis(naphthalene-1,4-diyloxy)]diphenyl-1,2-dicarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-benzophenonetetracarboxylic acid, 3,3',4,4'-diphenylsulfonetetracarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, 2,2',3,3'-biphenyltetracarboxylic acid, 2,2'-diphenoxy-4,4',5,5'-biphenyltetracarboxylic acid, 4,Tetracarboxylic acids such as 4'-[spiro(xanthene-9,9'-fluorene)-2,6-diylbis(oxycarbonyl)]diphthalic acid and 4,4'-[spiro(xanthene-9,9'-fluorene)-3,6-diylbis(oxycarbonyl)]diphthalic acid and their anhydrides. Among these, dianhydrides having two anhydride structures are suitable, and in particular, 4,4'-(2,2-hexafluoroisopropylidene)diphthalic acid dianhydride and 4,4'-oxydiphthalic acid dianhydride are preferred. In addition, aromatic tetracarboxylic acids can be used alone or in combination of two or more. When heat resistance is important, aromatic tetracarboxylic acids are preferably 50% by mass or more of the total tetracarboxylic acids, more preferably 60% by mass or more, further preferably 70% by mass or more, and further preferably 80% by mass or more. ,
[0063] Examples of the alicyclic tetracarboxylic acids include 1,2,3,4-cyclobutanetetracarboxylic acid, 1,2,3,4-cyclopentanetetracarboxylic acid, 1,2,3,4-cyclohexanetetracarboxylic acid, 1,2,4,5-cyclohexanetetracarboxylic acid, 3,3',4,4'-bicyclohexyltetracarboxylic acid, bicyclo[2,2,1]heptane-2,3,5,6-tetracarboxylic acid, bicyclo[2,2,2]octane-2,3,5,6-tetracarboxylic acid, bicyclo[2,2,2]oct-7-enyl-2,3,5,6-tetracarboxylic acid, tetrahydroanthracene-2,3,6,7-tetracarboxylic acid, tetradecahydro-1,4:5,8:9,10-trimethanoanthracene-2,3,6,7-tetracarboxylic acid, and decahydronaphthalene-2,3,6,7 -tetracarboxylic acid, decahydro-1,4:5,8-dimethanonaphthalene-2,3,6,7-tetracarboxylic acid, decahydro-1,4-ethyl-5,8-methanonaphthalene-2,3,6,7-tetracarboxylic acid, norbornane-2-spiro-α-cyclopentanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid (also known as "norbornane-2-spiro-2'-cyclopentanone-5'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid"), methylnorbornane-2-spiro-α-cyclopentanone-α'-spiro-2"-(methylnorbornane)-5,5",6,6"-tetracarboxylic acid, norbornane-2- Spiro-α-cyclohexanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid (also known as "norbornane-2-spiro-2'-cyclohexanone-6'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid"), methylnorbornane-2-spiro-α-cyclohexanone-α'-spiro-2"-(methylnorbornane)-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclopropanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclobutanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cycloheptanone-α'-spiro-2"-norbornane-5,5",6,6, 6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclooctanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclononanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclodecanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cycloundecanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclododecanone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclotridecanone-α'-spiro-2"-norbornane-5,Tetracarboxylic acids such as norbornane-2-spiro-α-cyclotetradeconone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-cyclopentadeconone-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, norbornane-2-spiro-α-(methylcyclopentanone)-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, and tetracarboxylic acids such as norbornane-2-spiro-α-(methylcyclohexanone)-α'-spiro-2"-norbornane-5,5",6,6"-tetracarboxylic acid, and their anhydrides. Among these, dianhydrides having two anhydride structures are preferred, and in particular, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclohexanetetracarboxylic dianhydride, and 1,2,4,5-cyclohexanetetracarboxylic dianhydride are preferred, 1,2,3,4-cyclobutanetetracarboxylic dianhydride and 1,2,4,5-cyclohexanetetracarboxylic dianhydride are more preferred, and 1,2,3,4-cyclobutanetetracarboxylic dianhydride is further preferred. It should be noted that these can be used alone or in combination of two or more. The copolymerization amount of alicyclic tetracarboxylic acids, for example, is preferably 50% by mass or more of the total tetracarboxylic acids, more preferably 60% by mass or more, further preferably 70% by mass or more, and further preferably 80% by mass or more, when transparency is important. ,
[0064] As tricarboxylic acids, aromatic tricarboxylic acids such as trimellitic acid, 1,2,5-naphthalenetricarboxylic acid, diphenyl ether-3,3',4'-tricarboxylic acid, and diphenyl sulfone-3,3',4'-tricarboxylic acid, or hydrogenated products of the above aromatic tricarboxylic acids such as hexahydrotrimellitic acid, alkylene glycol trimellitates such as ethylene glycol ditrimellitate, propylene glycol ditrimellitate, 1,4-butanediol ditrimellitate, and polyethylene glycol ditrimellitate, and monoanhydrides and esters thereof can be cited. Among these, monoanhydrides having one acid anhydride structure are preferred, and trimellitic acid anhydride and hexahydrotrimellitic acid anhydride are particularly preferred. In addition, these can be used alone or in combination.
[0065] As dicarboxylic acids, aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, 4,4'-oxy dibenzoic acid, or hydrides of the above aromatic dicarboxylic acids such as 1,6-cyclohexanedicarboxylic acid, oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecane dioic acid, dodecanedioic acid, 2-methylsuccinic acid, and acyl chlorides or esters thereof can be cited. Among these, aromatic dicarboxylic acids and hydrides thereof are preferred, and in particular, terephthalic acid, 1,6-cyclohexanedicarboxylic acid, 4,4'-oxy dibenzoic acid are preferred. In addition, dicarboxylic acids can be used alone or in combination.
[0066] In the present invention, there are no particular restrictions on the diamines or isocyanates used to obtain a polyimide with high colorless transparency, and aromatic diamines, aliphatic diamines, alicyclic diamines, aromatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, etc. commonly used in polyimide synthesis, polyamide-imide synthesis, and polyamide synthesis can be used. From the viewpoint of heat resistance, aromatic diamines are preferred, and from the viewpoint of transparency, alicyclic diamines are preferred. In addition, if aromatic diamines with a benzoxazole structure are used, while having high heat resistance, high elastic modulus, low thermal shrinkage, and low linear expansion coefficient can also be exhibited. Diamines and isocyanates can be used alone or in combination of two or more.
[0067] Examples of the aromatic diamines include 2,2'-dimethyl-4,4'-diaminobiphenyl, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1, 1,3,3,3-hexafluoropropane, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, m-aminobenzylamine, p-aminobenzylamine, 4-amino-N-(4-aminophenyl)benzamide, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 2,2'-trifluoromethyl-4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone Benzophenone, 3,4'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, bis[4-(4-aminophenoxy)phenyl]methane, 1,1-bis[4-(4-aminophenoxy)phenyl]ethane, 1,2-bis[4-(4-aminophenoxy)phenyl]ethane, 1,1-bis[4-(4-aminophenoxy)phenyl]propane, 1,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,3-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 1,1-bis[4-(4-aminophenoxy)phenyl] 1,3-bis[4-(4-aminophenoxy)phenyl]butane, 1,4-bis[4-(4-aminophenoxy)phenyl]butane, 2,2-bis[4-(4-aminophenoxy)phenyl]butane, 2,3-bis[4-(4-aminophenoxy)phenyl]butane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)-3-methylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3-methylphenyl]propane, 2-[4-(4-aminophenoxy)phenyl]-2-[4-(4-aminophenoxy)-3,5-dimethylphenyl]propane, 2,2-bis[4-(4-aminophenoxy)-3,5-dimethylphenyl]propane, 2,2-Bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 1,4-bis(3-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfoxide, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, 1,3-bis[4-(4-aminophenoxy)benzoyl]benzene, 1,3-bis[4-(3-aminophenoxy)phenyl] phenoxy)benzoyl]benzene, 1,4-bis[4-(3-aminophenoxy)benzoyl]benzene, 4,4'-bis[(3-aminophenoxy)benzoyl]benzene, 1,1-bis[4-(3-aminophenoxy)phenyl]propane, 1,3-bis[4-(3-aminophenoxy)phenyl]propane, 3,4'-diaminodiphenyl sulfide, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, bis[4-(3-aminophenoxy)phenyl]methane, 1,1-bis[4-(3-aminophenoxy)phenyl]ethane, 1,2-bis[4-(3-aminophenoxy)phenyl]ethane, bis[4-(3-aminophenoxy)phenyl]sulfoxide, 4,4'-bis[3-(4- 4,4'-bis[3-(3-aminophenoxy)benzoyl]diphenyl ether, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzophenone, 4,4'-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]diphenyl sulfone, bis[4-{4-(4-aminophenoxy)phenoxy}phenyl]sulfone, 1,4-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-aminophenoxy)phenoxy-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-trifluoromethylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-methylphenoxy)-α,α-dimethylbenzyl]benzene, 1,3-bis[4-(4-amino-6-cyanophenoxy)-α,α-dimethylbenzyl]benzene, 3,3'-diamino-4,4'-diphenoxybenzophenone, 4,4'-diamino-5,5'-diphenoxybenzophenone, 3,4'-diamino-4,5'-diphenoxybenzophenone, 3,3'-diamino-4-phenoxybenzophenone, 4,4'-diamino-5-phenoxybenzophenone, 3,4'-diamino-4-phenoxybenzophenone, 3,4'-diamino-5'-phenoxybenzophenone, 3,3'-diamino-4,4'-Bis(3-amino-4-phenoxybenzoyl)benzene, 1,4-bis(3-amino-4-phenoxybenzoyl)benzene, 1,3-bis(4-amino-5-phenoxybenzoyl)benzene, 1,4-bis(4-amino-5-phenoxybenzoyl)benzene, 1,3-bis(3-amino-4-phenoxybenzoyl)benzene, 1,4-bis(4-amino-5-phenoxybenzoyl)benzene, 1,3-bis(3-amino-4-phenoxybenzoyl)benzene, 1,4-bis(4-amino-5-phenoxybenzoyl)benzene, 1,3-bis(3-amino-4-phenoxybenzoyl)benzene 1,4-bis(3-amino-4-biphenyloxybenzoyl)benzene, 1,3-bis(4-amino-5-biphenyloxybenzoyl)benzene, 1,4-bis(4-amino-5-biphenyloxybenzoyl)benzene, 2,6-bis[4-(4-amino-α,α-dimethylbenzyl)phenoxy]benzonitrile, 4,4'-[9H-fluorene-9,9-diyl]dianiline (Also known as 9,9-bis(4-aminophenyl)fluorene), spiro(xanthene-9,9'-fluorene)-2,6-diylbis(oxycarbonyl)]dianiline, 4,4'-[spiro(xanthene-9,9'-fluorene)-2,6-diylbis(oxycarbonyl)]dianiline, 4,4'-[spiro(xanthene-9,9'-fluorene)-3,6-diylbis(oxycarbonyl)]dianiline, etc. In addition, part or all of the hydrogen atoms on the aromatic ring of the above aromatic diamine may be substituted with a halogen atom, an alkyl group or alkoxy group having 1 to 3 carbon atoms, or a cyano group, and part or all of the hydrogen atoms of the above alkyl group or alkoxy group having 1 to 3 carbon atoms may be substituted with a halogen atom. In addition, the aromatic diamines having the benzoxazole structure are not particularly limited, and examples thereof include 5-amino-2-(p-aminophenyl)benzoxazole, 6-amino-2-(p-aminophenyl)benzoxazole, 5-amino-2-(m-aminophenyl)benzoxazole, 6-amino-2-(m-aminophenyl)benzoxazole, 2,2'-p-phenylenebis(5-aminobenzoxazole), 2,2'-p-phenylenebis(6-aminobenzoxazole), 1-(5-aminobenzoxazole)-4-(6-aminobenzoxazole)benzene, 2,6-(4,4'-diaminodiphenyl)benzoxazole, )benzo[1,2-d:5,4-d']bisoxazole, 2,6-(4,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,4'-diaminodiphenyl)benzo[1,2-d:4,5-d']bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:5,4-d']bisoxazole, 2,6-(3,3'-diaminodiphenyl)benzo[1,2-d:4,5-d'] bisoxazole, etc. Among these, 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 4-amino-N-(4-aminophenyl)benzamide, 4,4'-diaminodiphenyl sulfone, and 3,3'-diaminobenzophenone are particularly preferred. In addition, the aromatic diamines can be used alone or in combination.
[0068] As alicyclic diamines, for example, 1,4-cyclohexanediamine, 1,4-diamino-2-methylcyclohexane, 1,4-diamino-2-ethylcyclohexane, 1,4-diamino-2-n-propylcyclohexane, 1,4-diamino-2-isopropylcyclohexane, 1,4-diamino-2-n-butylcyclohexane, 1,4-diamino-2-isobutylcyclohexane, 1,4-diamino-2-sec-butylcyclohexane, 1,4-diamino-2-tert-butylcyclohexane, 4,4'-methylenebis(2,6-dimethylcyclohexylamine) and the like can be mentioned. Among these, 1,4-cyclohexanediamine and 1,4-diamino-2-methylcyclohexane are particularly preferred, and 1,4-cyclohexanediamine is more preferred. In addition, alicyclic diamines can be used alone or in combination.
[0069] Examples of the diisocyanates include diphenylmethane-2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-dimethyldiphenylmethane-2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-diethyldiphenylmethane-2,4'-diisocyanate, -2,4'-diisocyanate, 3,2'- or 3,3'- or 4,2'- or 4,3'- or 5,2'- or 5,3'- or 6,2'- or 6,3'-dimethoxydiphenylmethane-2,4'-diisocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-3,3'-diisocyanate, diphenylmethane-3,4'-diisocyanate, diphenyl ether-4,4'-diisocyanate, benzophenone-4,4'- diisocyanate, diphenyl sulfone-4, 4'-diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, m-xylene diisocyanate, p-xylene diisocyanate, naphthalene-2,6-diisocyanate, 4,4'-(2,2-bis(4-phenoxyphenyl)propane) diisocyanate, 3,3'- or 2,2'-dimethylbiphenyl-4,4'-diisocyanate, 3,3'- or 2,2'-diethylbiphenyl- Aromatic diisocyanates such as 4,4'-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, and 3,3'-diethoxybiphenyl-4,4'-diisocyanate, and hydrogenated diisocyanates selected from these (for example, isophorone diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and hexamethylene diisocyanate). Among these, diphenylmethane-4,4'-diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, 3,3'-dimethylbiphenyl-4,4'-diisocyanate, naphthalene-2,6-diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and 1,4-cyclohexane diisocyanate are preferred from the viewpoints of low hygroscopicity, dimensional stability, price, and polymerizability. In addition, the diisocyanates may be used alone or in combination of a plurality thereof.
[0070] The transparent high heat-resistant film of the present invention may be a single-layer structure or a laminated structure of more than 2 layers. Based on the physical strength of the transparent high heat-resistant film and the easy peelability with the inorganic substrate, a laminated structure of more than 2 layers and a laminated structure of more than 3 layers are preferred. It should be noted that in this specification, the physical properties (yellowness index, total light transmittance, haze, etc.) of the transparent high heat-resistant film when it is a laminated structure of more than 2 layers, unless otherwise specified, refer to the values of the transparent high heat-resistant film as a whole.
[0071] The yellowness index (hereinafter also referred to as "yellowness index" or "YI") of the transparent high heat-resistant film of the present invention is preferably 10 or less, more preferably 7 or less, further preferably 5 or less, and further preferably 3 or less. The lower limit of the yellowness index of the transparent high heat-resistant film is not particularly limited, but in order to be used as a flexible electronic component, it is preferably 0.1 or more, more preferably 0.2 or more, and further preferably 0.3 or more.
[0072] The light transmittance of the transparent high heat-resistant film at a wavelength of 400nm in the present invention is preferably 70% or more, more preferably 72% or more, further preferably 75% or more, and further preferably 80% or more. The upper limit of the light transmittance of the transparent high heat-resistant film at a wavelength of 400nm is not particularly limited, but is preferably 99% or less, more preferably 98% or less, and further preferably 97% or less in order to be used as a flexible electronic component.
[0073] The total light transmittance of the transparent high heat-resistant film in the present invention is preferably 75% or more, more preferably 85% or more, further preferably 87% or more, and further preferably 88% or more. The upper limit of the total light transmittance of the transparent high heat-resistant film is not particularly limited, but is preferably 98% or less, more preferably 97% or less, for use as a flexible electronic component.
[0074] In the present invention, the haze of the transparent high heat-resistant film is preferably 1.0 or less, more preferably 0.8 or less, further preferably 0.5 or less, and further preferably 0.3 or less.
[0075] The thickness direction phase difference (Rth) of the transparent high heat-resistant film in the present invention is preferably 500nm or less, more preferably 300nm or less, further preferably 200nm or less, and further preferably 100nm or less. The lower limit of the Rth of the transparent high heat-resistant film is not particularly limited, but is preferably 0.1nm or more, more preferably 0.5nm or more, for use as a flexible electronic component.
[0076] The thickness of the transparent high heat-resistant film in the present invention is preferably 5 μm or more, more preferably 8 μm or more, further preferably 15 μm or more, and further preferably 20 μm or more. The upper limit of the thickness of the transparent high heat-resistant film is not particularly limited, but in order to be used as a flexible electronic component, it is preferably 200 μm or less, more preferably 150 μm or less, and further preferably 90 μm or less. If it is too thin, it is difficult to convey during film formation, and if it is too thick, it becomes difficult to convey with a roller.
[0077] It should be noted that the polyimide film with a linear expansion coefficient (CTE) represented by the present invention can also be achieved by stretching during the film formation process of the polyimide film. The stretching operation is to apply a polyimide solution on a support for the production of a polyimide film, dry it to form a polyimide film containing 1 to 50% by mass of a solvent, and further treat the polyimide film containing 1 to 50% by mass of a solvent at high temperature on the support for the production of the polyimide film or in a state peeled off from the support, and stretch it by 1.5 to 4.0 times in the MD direction and 1.4 to 3.0 times in the TD direction. At this time, an unstretched thermoplastic polymer film is used on the support for the production of the polyimide film, and after the thermoplastic polymer film and the polyimide film are stretched at the same time, the stretched polyimide film is peeled off from the thermoplastic polymer film, so that damage to the polyimide film can be prevented, especially during the stretching in the MD direction, and a higher-grade colorless and transparent polyimide film can be obtained.
[0078] The average linear expansion coefficient (CTE) of the transparent high heat-resistant film between 30°C and 300°C is 50ppm / K or less. Preferably, it is 45ppm / K or less, more preferably 40ppm / K or less, further preferably 30ppm / K or less, and particularly preferably 20ppm / K or less. In addition, it is preferably -5ppm / K or more, more preferably -3ppm / K or more, and further preferably 1ppm / K or more. If the CTE is within the range, it can ensure that the difference in linear expansion coefficient with the usual support (inorganic substrate) is small, and the transparent high heat-resistant film and the inorganic substrate can be peeled off even if used in a heating process, and warping with each support can be prevented. Here, CTE is a factor representing reversible expansion and contraction relative to temperature. It should be noted that the CTE of the transparent high heat-resistant film refers to the average value of the CTE in the mechanical direction (MD direction) and the CTE in the width direction (TD direction) of the transparent high heat-resistant film. The method for determining the CTE of the transparent high heat-resistant film is the method described in the embodiment.
[0079] The transparent high heat-resistant film may contain a filler. There is no particular limitation on the filler, and examples thereof include silica, carbon, ceramics, etc., of which silica is preferred. These fillers may be used alone or in combination of two or more. By adding fillers, it is possible to impart protrusions to the surface of the transparent high heat-resistant film, thereby increasing the slippage of the surface of the transparent high heat-resistant film. In addition, by adding fillers, the CTE and Rth of the transparent high heat-resistant film can also be suppressed to be low. The average particle size of the filler is preferably greater than 1 nm, more preferably greater than 5 nm, further preferably greater than 10 nm, and particularly preferably greater than 30 nm. In addition, it is preferably less than 1 μm, more preferably less than 500 nm, and further preferably less than 100 nm.
[0080] The content of filler in the transparent high heat-resistant film is preferably adjusted according to the average particle size of the filler. When the particle size of the filler is 30nm or more, it is preferably 0.01-5% by mass, more preferably 0.02-3% by mass, further preferably 0.05-2% by mass, and particularly preferably 0.1-1% by mass. On the other hand, when the average particle size is less than 30nm, it is preferably 1-50% by mass, more preferably 3-40% by mass, further preferably 5-30% by mass, and particularly preferably 10-20% by mass. By adjusting the content to the above range, the transparency of the transparent high heat-resistant film will not be lost, the high slip of the surface of the transparent high heat-resistant film can be ensured, and the CTE and Rth of the transparent high heat-resistant film can be further suppressed to a lower level.
[0081] The method of adding filler in the transparent high heat-resistant film is not particularly limited, and examples thereof include a method of adding a powder when making the above-mentioned polyamic acid (polyimide precursor) solution, polyimide solution, polyamide-imide solution, and polyamide solution, a method of adding in the form of a filler / solvent (suspension), etc., wherein in particular, a method of adding in a suspension is preferred. The suspension is not particularly limited, and examples thereof include a suspension in which a concentration of 20% by mass of silica with an average particle size of 10 nm is dispersed in N,N-dimethylacetamide (DMAC) (for example, "Snowtex (registered trademark) DMAC-ST" manufactured by Nissan Chemical Industries, a suspension in which a concentration of 20% by mass of silica with an average particle size of 80 nm is dispersed in N,N-dimethylacetamide (DMAC) (for example, "Snowtex (registered trademark) DMAC-ST-ZL" manufactured by Nissan Chemical Industries), etc.
[0082] In addition, when the transparent high heat-resistant film has a laminated structure with more than two layers, it is not ideal because the difference in CTE of each layer alone will cause warping. For this reason, the CTE difference between the first transparent high heat-resistant film layer in contact with the inorganic substrate and the second transparent high heat-resistant film layer adjacent to the first transparent high heat-resistant film that is not in contact with the inorganic substrate is preferably 40ppm / K or less, more preferably 30ppm / K or less, and further preferably 15ppm / K or less. In particular, the thickest layer in the second transparent high heat-resistant film is preferably within the above range. In addition, if the transparent high heat-resistant film has a symmetrical structure along the film thickness direction, it is not easy to warp, so it is preferred.
[0083] The CTE of the first transparent high heat-resistant film alone is preferably 20ppm / K or less. Since the CTE difference with the inorganic substrate becomes smaller, it is more preferably 15ppm / K or less, and further preferably 10ppm / K or less. In addition, there is no limit on the lower limit, but in order to be used as a flexible electronic component, it is preferably -10ppm / K or more, more preferably -5ppm / K or more, and further preferably 1ppm / K or more. The CTE of the first transparent high heat-resistant film refers to the average value of the CTE in the mechanical direction (MD direction) and the CTE in the width direction (TD direction) of the transparent high heat-resistant film, and the determination method is the method described in the embodiment.
[0084] The first transparent high heat-resistant film is preferably a transparent polyimide. In addition, when the second transparent high heat-resistant film further has a multi-layered structure, it is preferred that at least one layer of the second transparent high heat-resistant film is a transparent polyimide, and in the second transparent high heat-resistant film, the thickest layer is preferably a transparent polyimide. It is further preferred that all layers of the second transparent high heat-resistant polyimide are transparent polyimide.
[0085] The first transparent high heat-resistant film layer in contact with the inorganic substrate preferably contains a polyimide having the structure of the following formula 1 and / or the following formula 2. In the first transparent high heat-resistant film layer, the total amount of the polyimide having the structure of formula 1 and formula 2 is preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, particularly preferably 95% by mass or more, and may also be 100% by mass. If the polyimide having the structure of formula 1 and / or formula 2 is contained within the above range, the first transparent high heat-resistant film can exhibit excellent CTE.
[0086]
Chemistry 1
[0087]
[0088]
Chemistry 2
[0089]
[0090] The heat shrinkage rate of the transparent high heat-resistant film between 30° C. and 500° C. is preferably ±0.9%, and more preferably ±0.6%. The heat shrinkage rate is expressed as an irreversible expansion and contraction factor with respect to temperature.
[0091] The tensile fracture strength of the transparent high heat-resistant film is preferably 60MPa or more, more preferably 120MPa or more, and further preferably 240MPa or more. The upper limit of the tensile fracture strength is not particularly limited, and in fact is less than about 1000MPa. The tensile fracture strength is 60MPa or more, which can prevent the transparent high heat-resistant film from breaking when peeling off from an inorganic substrate. It should be noted that the tensile fracture strength of the transparent high heat-resistant film refers to the tensile fracture strength of the mechanical direction (MD direction) of the transparent high heat-resistant film and the average value of the tensile fracture strength of the width direction (TD direction). The method for determining the tensile fracture strength of the transparent high heat-resistant film is the method described in the embodiment. In addition, when a casting coater is used to coat the glass substrate, the two orthogonal directions of the parallel direction and the vertical direction are respectively regarded as (MD direction) and (TD direction) in the casting coater coating. The following tensile elongation at break and tensile elastic modulus are also the same.
[0092] The tensile elongation at break of the transparent high heat-resistant film is preferably 1% or more, more preferably 5% or more, and further preferably 20% or more. If the tensile elongation at break is 1% or more, the operability is excellent. It should be noted that the tensile elongation at break of the transparent high heat-resistant film refers to the average value of the tensile elongation at break in the mechanical direction (MD direction) and the tensile elongation at break in the width direction (TD direction) of the transparent high heat-resistant film. The method for determining the tensile elongation at break of the transparent high heat-resistant film is the method described in the embodiment.
[0093] The tensile elastic modulus of the transparent high heat-resistant film is preferably above 2 GPa, more preferably above 3 GPa, and further preferably above 4 GPa. If the tensile elastic modulus is above 3 GPa, the tensile deformation of the transparent high heat-resistant film when peeled off from an inorganic substrate is less and the operability is excellent. The tensile elastic modulus is preferably below 20 GPa, more preferably below 12 GPa, and further preferably below 10 GPa. If the tensile elastic modulus is below 20 GPa, the transparent high heat-resistant film can be used as a flexible film. It should be noted that the tensile elastic modulus of the transparent high heat-resistant film refers to the average value of the tensile elastic modulus in the mechanical direction (MD direction) and the tensile elastic modulus in the width direction (TD direction) of the high heat-resistant film. The method for determining the tensile elastic modulus of the transparent high heat-resistant film is according to the method described in the embodiment.
[0094] The thickness unevenness of the transparent high heat-resistant film is preferably 20% or less, more preferably 12% or less, further preferably 7% or less, and particularly preferably 4% or less. If the thickness unevenness is greater than 20%, it tends to be difficult to apply to a narrow portion. It should be noted that the thickness unevenness of the transparent high heat-resistant film is obtained by, for example, measuring the film thickness by randomly removing about 10 positions from the measured film with a contact-type film thickness meter, based on the following formula.
[0095] Film thickness unevenness (%)
[0096] =100×(maximum film thickness-minimum film thickness)÷average film thickness
[0097] The transparent high heat-resistant film is preferably obtained in the form of a rolled long transparent high heat-resistant film with a width of 300 mm or more and a length of 10 m or more during its manufacture, and is more preferably in the form of a roll-shaped transparent high heat-resistant film rolled on a winding core. If the transparent high heat-resistant film is rolled into a roll, the transportation of the transparent high heat-resistant film in the form of a roll becomes easier.
[0098] In order to ensure the handling and productivity of the transparent high heat-resistant film, it is preferred to add or contain about 0.03 to 3 mass % of a lubricant (particles) having a particle size of about 10 to 1000 nm to impart minute irregularities to the surface of the transparent high heat-resistant film to ensure sliding properties.
[0099] In the transparent high heat-resistant film with a stacked structure of more than two layers, in particular, the first transparent high heat-resistant film layer in contact with the inorganic substrate and the second transparent high heat-resistant film layer adjacent to the first transparent high heat-resistant film layer (hereinafter, also referred to as "the second transparent high heat-resistant film layer") preferably have less intermixing at the interface. If the thickness of the intermixing is small, since the transparent high heat-resistant film becomes easy to be thin-filmed, the thickness of the intermixing is preferably less than 800nm, more preferably less than 500nm, further preferably less than 200nm, further preferably less than 100nm, and particularly preferably less than 50nm. If the thickness of the intermixing is too large, the intermixing may occur on the outermost surface of the transparent high heat-resistant film, making it difficult to thin-film. The lower limit is not particularly limited, and in industry, it can be more than 10nm, and there is no problem with more than 20nm.
[0100] The method for forming a layer with less mixing is not particularly limited. It is preferred that the first transparent high heat-resistant film layer and the second transparent high heat-resistant film layer are simultaneously prepared by solution film-forming to prepare any one of the first transparent high heat-resistant film layer or the second transparent high heat-resistant film layer, and the next layer is prepared through a heating process. The heating process includes two types: an intermediate stage and a completed stage. After the heating process is completed, the next layer is prepared. Although it is possible to prepare something with less mixing, in most cases, the surface of the completed film has lost its reactivity, there are few functional groups on the surface, and the adhesion of the two layers is weak, which will cause problems in actual use. Therefore, even in the case of less mixing, it is preferred to produce an interface with more than 10nm of mixing.
[0101] By forming a two-layer film with materials (resins) having different physical properties, a film having various properties can be produced. Furthermore, by stacking them into a symmetrical structure in the thickness direction (for example, the first transparent high heat-resistant film layer / the second transparent high heat-resistant film layer / the first transparent high heat-resistant film layer), the balance of the CTE of the entire film can be well formed, and a film that is difficult to warp can be formed. In addition, by making any one layer an ultraviolet and infrared absorption layer, it is possible to have the characteristics of spectral characteristics, and by controlling the incidence and emission of light due to the layers with different refractive indices.
[0102] As means for producing a film having a layer structure of more than two layers, various methods can be considered, such as simultaneous coating using a T-die head that can discharge two layers at the same time, sequential coating after coating one layer, coating one layer and then drying it and then coating the next layer, coating the next layer after completing the film formation of one layer, or multi-layering by adding a heated laminate with a thermoplastic layer. In this patent, various existing coating methods and multi-layering techniques can be appropriately selected.
[0103] The thickness of the first transparent high heat-resistant film is preferably 0.1 μm or more. From the perspective of being less susceptible to the influence of mixing, it is more preferably 0.4 μm or more, further preferably 1 μm or more, further preferably 2 μm or more, and particularly preferably 3 μm or more. In addition, from the perspective of thinning the entire transparent high heat-resistant film, it is preferably 10 μm or less, more preferably 8 μm or less, and further preferably 5 μm or less.
[0104] <Inorganic substrate>
[0105] The inorganic substrate may be any plate-like object that can be used as a substrate composed of inorganic matter, for example, glass plates, ceramic plates, semiconductor chips, metals, etc. as the main body, as well as composites of these glass plates, ceramic plates, semiconductor chips, metals, substrates formed by stacking them, substrates dispersed with them, substrates containing these fibers, etc.
[0106] The glass plate includes quartz glass, high silica glass (96% silicon dioxide), soda-lime glass, lead glass, aluminoborosilicate glass, borosilicate glass (Pyrex (registered trademark)), borosilicate glass (alkali-free), borosilicate glass (microsheet), aluminosilicate glass, etc. Among them, glass having a linear expansion coefficient of 5 ppm / K or less is preferred, and as long as it is a commercially available product, "Corning (registered trademark) 7059", "Corning (registered trademark) 1737", "EAGLE" manufactured by Corning, "AN100" manufactured by Asahi Glass, "OA10" and "OA11G" manufactured by Nippon Electric Glass, "AF32" manufactured by SCHOTT, etc. are preferred as liquid crystal glass.
[0107] The semiconductor wafer is not particularly limited, and examples thereof include silicon wafers, germanium, silicon-germanium, gallium-arsenic, aluminum-gallium-indium, nitrogen-phosphorus-arsenic-antimony, SiC, InP (indium phosphide), InGaAs, GaInNAs, LT, LN, ZnO (zinc oxide), CdTe (cadmium telluride), ZnSe (zinc selenide), etc. Among them, the preferred wafer to be used is a silicon wafer, and a mirror-polished silicon wafer of 8 inches or more in size is particularly preferred.
[0108] The metal includes single element metals such as W, Mo, Pt, Fe, Ni, and Au; alloys such as Inconel, Monel, Nimonic, carbon copper, Fe-Ni Invar alloy, and super Invar alloy. In addition, it also includes a multilayer metal plate formed by adding other metal layers and ceramic layers to the above metals. At this time, if the CTE of the additional layer as a whole is low, Cu, Al, etc. can also be used in the main metal layer. As for the metal used as the additional metal layer, there is no limitation as long as it is a metal with strong adhesion to the polymer film and has the characteristics of non-diffusion, chemical resistance, and good heat resistance. Suitable examples include Cr, Ni, TiN, and Cu containing Mo.
[0109] As the ceramic plate in the present invention, Al 2 O 3 、Mullite、AlN、SiC、Crystallized glass、Cordierite、Spodumene、Pb-BSG+CaZrO 3 +Al 2 O 3 , Crystallized glass + Al 2 O 3 , crystallized Ca-BSG, BSG+quartz, BSG+quartz, BSG+Al 2 O 3 、Pb-BSG+Al 2 O 3 , glass-ceramics, microcrystalline glass materials (Zerodur material) and other ceramics for substrates.
[0110] The planar portion of the inorganic substrate is preferably sufficiently flat. Specifically, the PV value of the surface roughness is 50 nm or less, more preferably 20 nm or less, and further preferably 5 nm or less. Therefore, if it is rougher, the peel strength between the transparent high heat-resistant film layer and the inorganic substrate will become insufficient.
[0111] The thickness of the inorganic substrate is not particularly limited, and from the viewpoint of operability, it is preferably 10 mm or less, more preferably 3 mm or less, and further preferably 1.3 mm or less. The lower limit of the thickness is not particularly limited, but it is preferably 0.07 mm or more, more preferably 0.15 mm or more, and further preferably 0.3 mm or more. If it is too thin, it is easy to break and the operation becomes difficult. If it is too thick, it will become heavy and the operation becomes difficult.
[0112] <Laminated body>
[0113] The laminate of the present invention is a laminate formed by laminating the transparent high heat-resistant film and the inorganic substrate without substantially using an adhesive. When the transparent high heat-resistant film is a laminated structure having more than two layers, it preferably includes the first transparent high heat-resistant film in contact with the inorganic substrate and the second transparent high heat-resistant film layer adjacent to the first transparent high heat-resistant film layer that is not in contact with the inorganic substrate. The second transparent high heat-resistant film may further have a plurality of laminated structures. In addition, it may also be a structure in which both ends are inorganic substrates in the thickness direction of the laminate (for example, inorganic substrate / first transparent high heat-resistant film / second transparent high heat-resistant film / first transparent high heat-resistant film / inorganic substrate). At this time, the transparent high heat-resistant film and the inorganic substrate at both ends are substantially free of adhesive.
[0114] The shape of the laminate is not particularly limited, and may be a square or a rectangle. Preferably, it is a rectangle, and the length of the long side is preferably 300 mm or more, more preferably 500 mm or more, and further preferably 1000 mm or more. The upper limit is not particularly limited, and preferably, when used in industry, a substrate of a changeable size and material can be used. It can be 20000 mm or less, and there is no problem with 10000 mm or less.
[0115] The warpage amount of the laminate of the present invention when heated at 300°C is preferably 10 mm or less. In order to improve heat resistance, it is more preferably 8 mm or less, and further preferably 6 mm or less. The lower limit of the warpage amount is not particularly limited, and in industry, it can be 0.01 mm or more, and there is no problem with 0.1 mm or more.
[0116] <Adhesive>
[0117] There is substantially no adhesive layer between the inorganic substrate of the present invention and the transparent high heat-resistant film. Here, the adhesive layer described in the present invention refers to a material having a mass ratio of Si (silicon) component of less than 10% (less than 10% by mass). In addition, substantially not using (not interposed) means that the thickness of the adhesive layer between the inorganic substrate and the high heat-resistant film is preferably 0.4 μm or less, more preferably 0.1 μm or less, further preferably 0.05 μm or less, particularly preferably 0.03 μm or less, and most preferably 0 μm.
[0118] <Silane coupling agent (SCA)>
[0119] In the laminate, a silane coupling agent layer is preferably provided between the transparent high heat-resistant film and the inorganic substrate. In the present invention, a silane coupling agent refers to a compound containing 10% by mass or more of Si (silicon) components. It is further preferred that the structure has an alkoxy group. In addition, it is preferred not to add a methyl group. By using a silane coupling agent layer, the intermediate layer between the transparent high heat-resistant film and the inorganic substrate can be thinned, the degassing component during heating becomes less, and it is difficult to dissolve even in a wet method, and even if dissolution occurs, it is only a trace amount. In order to improve heat resistance, the silane coupling agent preferably contains more silicon oxide components, and in particular, it is preferred to have heat resistance at a temperature of about 400°C. The thickness of the silane coupling agent layer is preferably less than 0.2μm. As a range for use as a flexible electronic component, it is preferably less than 100nm (less than 0.1μm), more preferably less than 50nm, and more preferably 10nm. Usually, it is about 0.10μm or less. In addition, in the process of preferably reducing the silane coupling agent as much as possible, 5nm or less can also be used. If the thickness is less than 1 nm, the peel strength may be reduced or a portion may not be adhered, so it is preferably greater than 1 nm.
[0120] The silane coupling agent in the present invention is not particularly limited, but preferably has an amino group or an epoxy group. Specific examples of the silane coupling agent include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, 2-(3,4- 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilanevinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyl,diethoxysilane, 3-glycidoxypropyltriethoxysilane, p-phenylyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-amino 3-Aminopropyltrimethoxysilane hydrochloride, 3-ureidopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanatepropyltriethoxysilane, tris-(3-trimethoxysilylpropyl)isocyanurate, chloromethylphenethyltrimethoxysilane, chloromethyltrimethoxysilane, etc. Among these, preferred ones include N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, aminophenyltrimethoxysilane, aminophenethyltrimethoxysilane, and aminophenylaminomethylphenethyltrimethoxysilane. When heat resistance is required in the process, a coupling agent in which Si and amino groups are linked by aromatic groups is preferred.
[0121] The peel strength between the transparent high heat-resistant film and the inorganic substrate needs to be 0.3N / cm or less. Thus, after forming a device on the transparent high heat-resistant film, it becomes very easy to peel the transparent high heat-resistant film from the inorganic substrate. Therefore, it is possible to manufacture mass-produced device connectors, and the manufacture of flexible electronic components becomes easy. The peel strength is preferably 0.25N / cm or less, more preferably 0.2N / cm or less, further preferably 0.15N / cm or less, and particularly preferably 0.12N / cm or less. In addition, it is preferably 0.03N / cm or more. In order that the laminate will not peel off when the device is formed on the transparent high heat-resistant film, it is more preferably 0.06N / cm or more, further preferably 0.08N / cm or more, and particularly preferably 0.1N / cm or more. The peel strength is the value of the laminate after the transparent high heat-resistant film and the inorganic substrate are bonded and heat treated at 100°C for 10 minutes in an atmospheric atmosphere (initial peel strength). Furthermore, it is preferred that the peel strength of the laminate after further heat-treating the laminate at 300° C. for 1 hour in a nitrogen atmosphere during the initial peel strength measurement also be within the above range (peel strength after heat treatment at 300° C.).
[0122] The laminate of the present invention, for example, can be made by the following process. First, at least one surface of the inorganic substrate is treated with an alkane coupling agent, and the surface treated with the silane coupling agent is overlapped with the transparent high heat-resistant film, and the laminate can be obtained by pressurizing and laminating the two. In addition, at least one surface of the transparent high heat-resistant film is first treated with a silane coupling agent, and the surface treated with the silane coupling agent is overlapped with the inorganic substrate, and the laminate can also be obtained by pressurizing and laminating the two. In addition, when the transparent high heat-resistant film is a laminated structure having more than two layers, it is preferred to overlap the first transparent high heat-resistant film and the inorganic substrate. As a pressurization method, it can be exemplified by pressing or laminating in the atmosphere with normal pressing or laminating or pressing or laminating in a vacuum. In order to obtain an overall stable bonding strength and a large-sized laminate (for example, greater than 200mm), lamination in the atmosphere is preferred. In contrast, if it is a small-sized laminate of about 200mm or less, it is preferably pressed in a vacuum. The vacuum degree can be obtained by using a common oil rotary pump, which is about 10Torr or less. The preferred pressure is 1 MPa to 20 MPa, more preferably 3 MPa to 10 MPa. If the pressure is too high, the substrate may be damaged, and if the pressure is too low, there may be a part that is not closely attached. The preferred temperature is 90°C to 300°C, more preferably 100°C to 250°C. If the temperature is too high, the film may be damaged, and if the temperature is too low, the adhesion is weak.
[0123] <Production of films with electronic components (flexible electronic components)>
[0124] By using the laminate, flexible electronic components can be easily manufactured using existing electronic component manufacturing equipment and processes. Specifically, electronic components are formed on the transparent high heat-resistant film of the laminate, and the transparent high heat-resistant film is peeled off from the laminate to manufacture flexible electronic components.
[0125] The electronic components in this specification refer to single-sided, double-sided or multi-layer circuit substrates with electrical circuits, including electronic circuits with active components such as transistors and diodes or passive devices such as resistors, capacitors, and inductors, as well as sensor components for sensing pressure, temperature, light, humidity, etc., biosensor components, image display components such as light-emitting components, liquid crystal displays, electrophoretic displays, and self-luminous displays, wireless and wired communication components, computing components, storage components, MEMS components, solar cells, thin-film transistors, etc.
[0126] In addition, the wiring substrate also includes an interposer function as an electrode that penetrates the polyimide. After roughly penetrating, the step of making a through electrode after peeling off the inorganic substrate can be greatly omitted. Known methods can be used to make through holes. For example, in a transparent high heat-resistant film, a through hole is punched by a UV nano laser. Then, for example, by applying the through hole used in a double-sided printed wiring board or the conventional method in the via hole in a multilayer printed wiring board, the through hole is filled with a conductive metal, and these methods of forming a wiring pattern with metal as needed are added. The transparent high heat-resistant film can also be bonded to the inorganic substrate after the through electrode is set as described above. It can also be the case that the inorganic substrate and the transparent high heat-resistant film are bonded to make the through electrode. It is also possible to penetrate the transparent high heat-resistant film to metallize the place, but it is also possible to open a hole from one side of the transparent high heat-resistant film and metallize the place in a state where the surface on the opposite side is not penetrated.
[0127] In the method for producing a flexible electronic component of the present specification, after forming a device on the transparent high heat-resistant film of the laminate produced by the above method, the transparent high heat-resistant film is peeled off from the inorganic substrate.
[0128] <Peeling off the transparent high heat-resistant film with the device attached from the inorganic substrate>
[0129] There is no particular limitation on the method of peeling the transparent high heat-resistant film with the device from the inorganic substrate. It can be a method of rolling up from the end using tweezers, etc., a method of cutting the transparent high heat-resistant film, pasting an adhesive tape on one side of the cut portion, and rolling up from the tape portion, a method of vacuuming one side of the cut portion of the high heat-resistant film, and rolling up from the portion, etc. It should be noted that when peeling, if a small curvature is generated on the cut portion of the high heat-resistant film, stress will be applied to the device of the portion, which may damage the device, so it is preferred to peel off in a state of large curvature as much as possible. For example, it is preferred to roll up while winding with a roller with a large curvature, or to roll up using a machine constructed by placing a roller with a large curvature on the peeling portion.
[0130] As a method for cutting the transparent high heat-resistant film, there are methods of cutting the transparent high heat-resistant film with a cutting tool such as a cutter, a method of cutting the transparent high heat-resistant film by relative scanning of a laser and a laminate, a method of cutting the transparent high heat-resistant film by relative scanning of a water jet and a laminate, a method of cutting the transparent high heat-resistant film by gradually cutting into a plurality of glass layers using a semiconductor chip cutting device, etc., and the method is not particularly limited. For example, when adopting the above methods, it is also possible to appropriately use techniques such as adding ultrasonic waves to the cutting tool, applying back and forth motions and up and down motions, etc. to improve cutting performance.
[0131] In addition, a method of pre-pasting other reinforcing substrates on the peeled portion and peeling off the reinforcing substrate as a whole is also useful. When the peeled flexible electronic component is the backplane of a display device, the front plane of the display device is first pasted, and after integration on the inorganic substrate, the two are peeled off at the same time, so as to obtain a flexible display device.
[0132] [Example]
[0133] Hereinafter, the present invention will be described in detail using examples, but the present invention is not limited to the following examples unless the gist of the present invention is exceeded.
[0134] [Production Example 1 (Production of Polyimide Solution 1)]
[0135] In a reaction vessel equipped with a nitrogen inlet tube, a Dean-Stark apparatus, a reflux tube, and a stirring rod, 19.86 parts by mass of 4,4'-diaminodiphenyl sulfone (4,4'-DDS), 4.97 parts by mass of 3,3'-diaminodiphenyl sulfone (3,3'-DDS), and 80 parts by mass of γ-butyrolactone (GBL) were added while introducing nitrogen. Then, 31.02 parts by mass of 4,4'-oxydiphthalic dianhydride (ODPA), 24 parts by mass of GBL, and 13 parts by mass of toluene were added at room temperature, and the temperature was raised to an internal temperature of 160°C, and refluxed at 160°C for 1 hour to carry out imidization. After the imidization was completed, the temperature was raised to 180°C, and the reaction was continued while removing toluene. After 12 hours of reaction, the mixture was removed from the oil bath and returned to room temperature. GBL was added to a solid content concentration of 20 mass % to obtain a polyimide solution 1 having a reduced viscosity of 0.70 dl / g (molar ratio of 4,4'-DDS / 3,3'-DDS / / ODPA = 0.80 / 0.20 / / 1.00).
[0136] [Production Example 2 (Production of polyamic acid solution 2)]
[0137] After nitrogen substitution in a reaction vessel equipped with a nitrogen inlet pipe, a reflux pipe, and a stirring rod, 32.02 parts by mass of 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl (TFMB) and 279.9 parts by mass of N,N-dimethylacetamide (DMAc) were added until they were completely dissolved, and then 9.81 parts by mass of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA) and 15.51 parts by mass of 4,4'-oxydiphthalic dianhydride (ODPA) were added in batches in solid form, respectively, and stirred at room temperature for 24 hours. Then, a polyamic acid solution 2 having a solid content of 17% by mass and a reduced viscosity of 3.60 dl / g was obtained (TFMB / / CBDA / ODPA molar ratio = 1.00 / / 0.50 / 0.50).
[0138] [Production Example 3 (Production of polyamic acid solution 3)]
[0139] After nitrogen substitution in a reaction container equipped with a nitrogen inlet tube, a reflux tube, and a stirring rod, 22.73 parts by mass of 4,4'-diaminobenzamidebenzene (DABAN), 201.1 parts by mass of N,N-dimethylacetamide (DMAc), and a dispersion of colloidal silica dispersed in dimethylacetamide ("SNOWTEX (registered trademark) DMAC-ST-ZL" manufactured by Nissan Chemical Industries) as a lubricant were added and completely dissolved, and then 19.32 parts by mass of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA) was added portionwise in a solid form, followed by stirring at room temperature for 24 hours. Then, 173.1 parts by mass of DMAc was added for dilution to obtain a polyamic acid solution 3 (molar ratio of DABAN / CBDA=1.00 / 0.985) having an NV (solid content) of 10% by mass and a reduced viscosity of 3.10 dl / g.
[0140] [Production Example 4 (Production of polyamic acid solution 4)]
[0141] After nitrogen substitution in a reaction container equipped with a nitrogen inlet tube, a reflux tube, and a stirring rod, 32.02 parts by mass of 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl (TFMB), 252.1 parts by mass of N,N-dimethylacetamide (DMAc), and a dispersion of colloidal silica dispersed in dimethylacetamide ("SNOWTEX (registered trademark) DMAC-ST-ZL" manufactured by Nissan Chemical Industries) as a lubricant were added and completely dissolved, and then 19.61 parts by mass of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA) was added portionwise in a solid form, followed by stirring at room temperature for 24 hours. Then, 165.7 parts by mass of DMAc was added for dilution to obtain a polyamic acid solution 4 having an NV of 11 mass % and a reduced viscosity of 3.50 dl / g (the molar ratio of TFMB / CBDA=1.00 / 1.00).
[0142] [Production Example 5]
[0143] After adding and dissolving 205.8 parts by mass of 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene (p-6FAPB) and 1200 parts by mass of N,N-dimethylacetamide, 93.8 parts by mass of cyclobutanetetracarboxylic dianhydride (CBDA) were added in batches in a solid form while cooling the reaction container, and stirred at room temperature for 12 hours. Subsequently, 1.0 parts by mass of 4-methylcyclohexane-1,2-dicarboxylic anhydride (MHHPA) was added, stirred for 4 hours, and then diluted with 1000 parts by mass of N,N-methylacetamide to obtain a polyamic acid solution 5 having a reduced viscosity of 5.28 dl / g (molar ratio of p-6FAPB / / CBDA / MHHPA = 0.480 / / 0.478 / 0.0059).
[0144] [Production Example 6 (Production of Polyamic Acid Solution 6)]
[0145] After nitrogen substitution in a reaction container equipped with a nitrogen inlet pipe, a reflux pipe and a stirring rod, 22.0 parts by mass of 2,2'-bis(trifluoromethyl)benzidine (TFMB), 252.1 parts by mass of N,N-dimethylacetamide (DMAc) and a dispersion of colloidal silica dispersed in dimethylacetamide as a lubricant ("SNOWTEX (registered trademark) DMAC-ST-ZL" manufactured by Nissan Chemical Industries, Ltd.) were completely dissolved (so that the silica (lubricant) accounted for 0.4% by mass of the total polymer solid content in the polyamic acid solution), and then 22.0 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added portionwise in a solid form, followed by stirring at room temperature for 24 hours. Then, 165.7 parts by mass of DMAc was added for dilution to obtain a polyamic acid solution 6 (TFMB / BPDA molar ratio = 0.075 / 0.069) having a solid content (NV) of 11% by mass and a reduced viscosity of 3.5 dl / g.
[0146] [Production Example 7 (Production of Polyamic Acid Solution 7)]
[0147] After replacing the atmosphere in a reaction vessel equipped with a nitrogen inlet tube, a reflux tube, and a stirring rod with nitrogen, 22.00 parts by mass of 2,2'-bis(trifluoromethyl)benzidine (TFMB), 252.1 parts by mass of N,N-dimethylacetamide (DMAc) as a lubricant (a dispersion of colloidal silica dispersed in dimethylacetamide ("SNOWTEX (registered trademark) DMAC-ST-ZL" manufactured by Nissan Chemical Industries, Ltd.), and silica (lubricant) (0.4% by mass of the total polymer solid content in the polyamic acid solution) were added and completely dissolved, and then 11.01 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and 10.98 parts by mass of 4,4'-oxydiphthalic dianhydride (ODPA) were added portionwise in a solid form, followed by stirring at room temperature for 24 hours. Then, 165.7 parts by mass of DMAc was added for dilution to obtain a polyamic acid solution 7 (molar ratio of TFMB / ODPA / BPDA = 0.068 / 0.035 / 0.037) having a solid content (NV) of 11% by mass and a reduced viscosity of 3.5 dl / g.
[0148] [Production Example 8 (Production of Polyamic Acid Solution 8)]
[0149] After nitrogen substitution in a reaction vessel equipped with a nitrogen inlet tube, a reflux tube, and a stirring rod, 33.36 parts by mass of 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl (TFMB) and 336.31 parts by mass of N-methyl-2-pyrrolidone (NMP) were added and completely dissolved, and then 9.81 parts by mass of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 11.34 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), and 4.85 parts by mass of 4,4'-oxydiphthalic dianhydride (ODPA) were added in batches in solid form, and stirred at room temperature for 24 hours. Subsequently, a polyamic acid solution 8 having a solid content of 15% by mass and a reduced viscosity of 3.50 dl / g was obtained (TFMB / / CBDA / BPDA / ODPA molar ratio = 1.00 / / 0.48 / 0.37 / 0.15).
[0150] [Production Example 9 (Production of Polyamic Acid Solution 9)]
[0151] After nitrogen substitution in a reaction container equipped with a nitrogen inlet tube, a reflux tube and a stirring rod, 33.36 parts by mass of 2,2'-bis(trifluoromethyl)benzidine (TFMB), 270.37 parts by mass of N-methyl-2-pyrrolidone (NMP) and a dispersion in which colloidal silica is dispersed in dimethylacetamide ("Snowtex (registered trademark) DMAC-ST" manufactured by Nissan Chemical Industries) were added until the silica was completely dissolved so that the silica accounted for 0.14% by mass of the total polymer solid content in the polyamic acid solution. Then, 9.81 parts by mass of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 11.34 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and 4.85 parts by mass of 4,4'-oxydiphthalic dianhydride (ODPA) were added in portions in a solid form, followed by stirring at room temperature for 24 hours. Then, 165.7 parts by mass of DMAc was added for dilution to obtain a polyamic acid solution 9 having a solid content of 18% by mass and a reduced viscosity of 2.7 dl / g (molar ratio of TFMB / / CBDA / BPDA / ODPA = 1.00 / / 0.48 / 0.37 / 0.15).
[0152] [Production Example 10 (Production of Polyamic Acid Solution 10)]
[0153] After nitrogen substitution in a reaction container equipped with a nitrogen inlet pipe, a reflux pipe, and a stirring rod, 33.36 parts by mass of 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl (TFMB), 336.31 parts by mass of N-methyl-2-pyrrolidone (NMP), and a dispersion of colloidal silica dispersed in dimethylacetamide ("SNOWTEX (registered trademark) DMAC-ST-ZL" manufactured by Nissan Chemical Industries) as a lubricant were added to make dimethyl acetamide. Silicon oxide (lubricant) is 0.3% by mass of the total polymer solid content in the polyamic acid solution, and it is completely dissolved. Then, 9.81 parts by mass of 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 11.34 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), and 4.85 parts by mass of 4,4'-oxydiphthalic dianhydride (ODPA) are added in batches in solid form, and stirred at room temperature for 24 hours. Subsequently, a polyamic acid solution 10 with a solid content of 15% by mass and a reduced viscosity of 3.50 dl / g is obtained (the molar ratio of TFMB / / CBDA / BPDA / ODPA = 1.00 / / 0.48 / 0.37 / 0.15).
[0154] [Production Example 1 (Production of polyimide films A, A2 and A3)]
[0155] The polyamic acid solution 3 obtained in manufacturing example 3 was applied on the surface of the non-lubricated material of polyethylene terephthalate film A4100 (manufactured by Toyobo Co., Ltd.) using a comma coater so that the final film thickness was adjusted to 3 μm. The polyethylene terephthalate film A4100 was passed into a hot air furnace and rolled up, and then dried at 100°C for 10 minutes. After rolling up, it was set on one side of the comma coater, and then, on the dried product of the polyamic acid solution 3, the polyimide solution 1 obtained in manufacturing example 1 was applied so that the final film thickness was 15 μm. It was dried at 100°C for 10 minutes. The self-supporting polyamic acid film obtained after drying was peeled off from the support, passed through a pin tenter having a pin plate equipped with pins, inserted the pins into the ends of the film to hold it, and conveyed by adjusting the interval between the pin plates so that the film would not break and would not produce unnecessary slack, and heated at 200° C. for 3 minutes, 250° C. for 3 minutes, and 300° C. for 6 minutes to carry out imidization reaction. Subsequently, it took 2 minutes to cool to room temperature, and the portions with poor planarity at both ends of the film were cut off with a cutter, and wound into a coiled material to obtain 500 m of a polyimide film A1 with a width of 450 mm.
[0156] [Production example 2]
[0157] On the surface of the non-lubricating material of polyethylene terephthalate film A4100 (manufactured by Toyobo Co., Ltd.), the polyamic acid solution 3 obtained in manufacturing example 3 is coated using a comma coater to make the final film thickness 3 μm, and then, on the polyamic acid solution 3, the polyimide solution 1 obtained in manufacturing example 1 is coated using a die coater to make the final film thickness 15 μm. It is dried at 110°C for 10 minutes. The self-supporting polyamic acid film obtained after drying is peeled off from the A4100 film as a support, passed through a pin tenter having a pin plate equipped with pins, and held by inserting the pins into the ends of the film, and conveyed in a manner that the film will not break and does not produce unnecessary relaxation, adjusting the pin plate interval, and heated at 200°C for 3 minutes, 250°C for 3 minutes, and 300°C for 6 minutes to carry out imidization reaction. Then, the film was cooled to room temperature over 2 minutes, and the portions with poor planarity at both ends of the film were cut off with a cutter, and the film was wound into a roll to obtain 500 m of a polyimide film A2 with a width of 450 mm.
[0158] [Production example 3]
[0159] For a part of the polyimide film A2, the starting end was temporarily fixed with a polyimide tape on the surface of the non-lubricating material of polyethylene terephthalate film A4100 (manufactured by Toyobo Co., Ltd.), and the polyamic acid solution 3 obtained in Manufacturing Example 3 was applied thereon using a die coater so that the final film thickness was 3 μm. At this time, the polyamic acid solution 3 side of the polyimide film A2 was in contact with the polyethylene terephthalate film A4100, and the polyimide solution 1 side was applied. These of the polyimide film A2 were dried at 90° C. for 10 minutes. After drying, the polyimide tape was peeled off and separated from the polyethylene terephthalate film A4100, and passed into a pin tenter having a pin plate equipped with pins, and the pins were inserted into the ends of the film to hold it, and the pin plate interval was adjusted so that the film would not break and unnecessary slack would not occur, and the film was transported, and heated at 200°C for 3 minutes, 250°C for 3 minutes, and 300°C for 6 minutes to carry out imidization reaction. Subsequently, it took 2 minutes to cool to room temperature, and the portions with poor flatness at both ends of the film were cut off with a cutter, and it was wound into a roll to obtain 200m of a polyimide film A3 with a width of 400mm.
[0160] [Production Example 4 (Production of polyimide film B)]
[0161] A polyimide film B was obtained in the same manner as in the polyimide film A1 of Production Example 1 except that the polyamic acid solution 3 obtained in Production Example 3 was changed to the polyamic acid solution 4 obtained in Production Example 4.
[0162] [Production Example 5 (Production of polyimide film C)]
[0163] A polyimide film C was obtained in the same manner as in the preparation of the polyimide film A1 of Preparation Example 1, except that the polyimide solution 1 obtained in Preparation Example 1 was changed to the polyamic acid solution 2 obtained in Preparation Example 2 and the final film thickness was adjusted to 1 μm.
[0164] [Production Example 6 (Production of polyimide film D)]
[0165] On the surface of the non-lubricated material of polyethylene terephthalate film A4100 (manufactured by Toyobo Co., Ltd.), the polyamic acid solution 3 obtained in Manufacturing Example 3 is applied using a comma coater to adjust the final film thickness to 3μm. It is dried at 90-110°C for 10 minutes. After winding, it is set on one side of the comma coater, and then, on the dried product of the polyamic acid solution 3, the polyimide solution 1 obtained in Manufacturing Example 1 is applied to make the final film thickness 15μm. It is dried at 90-110°C for 10 minutes. After it is wound, it is set on one side of the comma coater, and then, on the dried product of the polyamic acid solution 1, the polyimide solution 3 obtained in Manufacturing Example 3 is applied to make the final film thickness 3μm. It is dried at 90-110°C for 10 minutes. The self-supporting polyamic acid film obtained after drying was peeled off from the support, passed into a pin tenter having a pin plate equipped with pins, inserted the pins into the ends of the film to hold it, and conveyed by adjusting the interval between the pin plates so that the film would not break and would not produce unnecessary relaxation, and heated at 200° C. for 3 minutes, 250° C. for 3 minutes, and 300° C. for 6 minutes to carry out imidization reaction. Subsequently, it took 2 minutes to cool to room temperature, and the portions with poor planarity at both ends of the film were cut off with a cutter, and wound into a coiled material to obtain a polyimide film D1 with a length of 500 m and a width of 450 mm.
[0166] [Production Example 7 (Production of polyimide film D2)]
[0167] A polyimide film D2 was obtained in the same manner as in Production Example 6 except that the coating thickness was adjusted so that the final film thickness of the polyimide solution 1 would be 19 μm.
[0168] [Production Example 8 (Production of polyimide film E)]
[0169] The polyimide solution 1 obtained in Manufacturing Example 1 was applied to a glass substrate using a cast coater, and heated from room temperature to 300° C. in a nitrogen atmosphere and maintained at 300° C. for 1 hour to perform thermal imidization to obtain a polyimide film / glass laminate. The obtained laminate was then immersed in water, peeled off, and dried to obtain a polyimide film E with a film thickness of 15 μm.
[0170] [Production Example 9 (Production of polyimide film F)]
[0171] A polyimide film F was obtained in the same manner as in Preparation Example 8 except that the polyimide solution 1 obtained in Preparation Example 1 was changed to the polyamic acid solution 2 obtained in Preparation Example 2.
[0172] [Production Example 10 (Production of polyimide film G)]
[0173] A polyimide film G was obtained in the same manner as in Production Example 1 except that the polyamic acid solution 3 was changed to the polyamic acid solution 2.
[0174] [Production Example 11 (Production of polyimide film H)]
[0175] A polyimide film H was obtained in the same manner as in Preparation Example 8 except that the polyimide solution 1 obtained in Preparation Example 1 was changed to the polyamic acid solution 3.
[0176] [Production Example 12 (Production of polyimide film I)]
[0177] A polyimide film I was obtained in the same manner as in Preparation Example 8 except that the polyimide solution 1 obtained in Preparation Example 1 was changed to the polyamic acid solution 4.
[0178] [Production Example 13 (Production of polyimide film J)]
[0179] A polyimide film J was obtained in the same manner as in Preparation Example 8 except that the polyimide solution 1 obtained in Preparation Example 1 was changed to the polyamic acid solution 2 and the designed film thickness was changed to 25 μm.
[0180] [Production Example 14 (Production of polyimide film K)]
[0181] A polyimide film K was obtained in the same manner as in Preparation Example 8 except that the polyimide solution 1 obtained in Preparation Example 1 was changed to the polyamic acid solution 5 .
[0182] [Production Example 15 (Production of polyimide film L)]
[0183] A polyimide film L was obtained in the same manner as in the polyimide film A of Production Example 1 except that the polyimide solution 1 was changed to the polyamic acid solution 5 .
[0184] [Production Example 16 (Production of polyimide film M)]
[0185] The polyamide acid solution 6 obtained in manufacturing example 6 was applied to the non-lubricated surface of polyethylene terephthalate film A4100 (manufactured by Toyobo Co., Ltd.) using a comma coater to adjust the final film thickness to 0.5 μm. The polyethylene terephthalate film A4100 was passed into a hot air furnace and rolled up, and then dried at 100°C for 10 minutes. After rolling up, it was set on one side of the comma coater, and then the polyimide solution 1 obtained in manufacturing example 1 was applied to the dried product of the polyamide acid solution 6 to make the final film thickness 15 μm. It was dried at 100°C for 10 minutes. The self-supporting polyamic acid film obtained after drying was peeled off from the support, passed into a pin tenter having a pin plate equipped with pins, inserted the pins into the ends of the film to hold it, and conveyed by adjusting the interval between the pin plates so that the film would not break and would not produce unnecessary relaxation, and heated at 200° C. for 3 minutes, 250° C. for 3 minutes, and 300° C. for 6 minutes to carry out imidization reaction. Subsequently, it took 2 minutes to cool to room temperature, and the portions with poor planarity at both ends of the film were cut off with a cutter, and wound into a coiled material to obtain 500 m of a polyimide film M with a width of 450 mm.
[0186] [Production Example 17 (Production of polyimide film N)]
[0187] A polyimide film N was obtained in the same manner as in Production Example 16 except that the polyamic acid solution 6 was changed to the polyamic acid solution 7.
[0188] [Production Example 18 (Production of polyimide film O)]
[0189] On the surface of the non-lubricating material of polyethylene terephthalate film A4100 (manufactured by Toyobo Co., Ltd.), a comma coater is used to apply the polyimide solution 1 obtained in manufacturing example 1 so that the final film thickness is 15 μm, and then, on the polyamic acid solution 1, the polyimide solution 3 obtained in manufacturing example 3 is applied by a die coater so that the final film thickness is 0.5 μm. It is dried at 110°C for 10 minutes. The self-supporting polyamic acid film obtained after drying is peeled off from the A4100 film as a support, and is passed into a pin tenter having a pin plate equipped with pins, and the pin plate interval is adjusted to convey the film in a manner that the film will not break and does not produce unnecessary relaxation, and is heated under the conditions of 3 minutes at 200°C, 3 minutes at 250°C, and 6 minutes at 300°C to carry out imidization reaction. Then, the film was cooled to room temperature over 2 minutes, and the portions with poor planarity at both ends of the film were cut off with a cutter, and the film was wound into a roll to obtain 500 m of a polyimide film O with a width of 450 mm.
[0190] [Production Example 19 (Production of polyimide film P)]
[0191] A polyimide film P was obtained by the same operation as in Preparation Example 16, except that polyamic acid solution 6 was changed to polyamic acid solution 3, polyimide solution 1 was changed to polyamic acid solution 8, and the heating conditions of the imidization reaction were changed to 200°C for 3 minutes, 250°C for 3 minutes, 300°C for 3 minutes, and 350°C for 3 minutes.
[0192] [Production Example 20 (Production of polyimide film Q)]
[0193] Polyimide film Q was obtained by the same operation as in Preparation Example 16, except that polyamic acid solution 6 was changed to polyamic acid solution 3, polyimide solution 1 was changed to polyamic acid solution 9, and the heating conditions of the imidization reaction were changed to 200°C for 3 minutes, 250°C for 3 minutes, 300°C for 3 minutes, and 350°C for 3 minutes.
[0194] [Production Example 21 (Production of polyimide film R)]
[0195] A polyimide film R was obtained in the same manner as in Production Example 16 except that the polyimide solution 1 was changed to the polyamic acid solution 9.
[0196] [Production Example 22 (Production of polyimide film S)]
[0197] A polyimide film S was obtained in the same manner as in Production Example 8 except that the polyimide solution 1 was changed to the polyamic acid solution 8.
[0198] [Production Example 23 (Production of polyimide film T)]
[0199] A polyimide film T was obtained in the same manner as in Production Example 8 except that the polyimide solution 1 was changed to the polyamic acid solution 9.
[0200] [Production Example 24 (Production of polyimide film U)]
[0201] Polyimide film U was obtained by the same operation as in Preparation Example 16, except that polyamic acid solution 6 was changed to polyamic acid solution 10, polyimide solution 1 was changed to polyamic acid solution 8, and the heating conditions of the imidization reaction were changed to 200°C for 3 minutes, 250°C for 3 minutes, 300°C for 3 minutes, and 350°C for 3 minutes.
[0202] <Measurement of polyimide film thickness>
[0203] The thickness of polyimide films A to U was measured using a micrometer (Millitron 1245D, manufactured by FEINPRUF).
[0204] <Tensile elastic modulus, tensile breaking strength and tensile breaking elongation of polyimide film>
[0205] Polyimide films A to U were cut into 100 mm × 10 mm strips in the machine direction (MD direction) and the width direction (TD direction) as test pieces. A tensile tester (manufactured by Shimadzu Corporation, Autograph (R) equipment name AG-5000A) was used to measure the tensile elastic modulus, tensile breaking strength and tensile breaking elongation in the MD direction and TD direction under the conditions of a tensile speed of 50 mm / min and a chuck spacing of 40 mm. The results are shown in Tables 1 and 2.
[0206] <Coefficient of Linear Expansion (CTE) of Polyimide Film>
[0207] The polyimide films A to U were measured for shrinkage under the following conditions along the machine direction (MD direction) and the width direction (TD direction), and the shrinkage / temperature was measured at intervals of 15°C, such as 30°C to 45°C and 45°C to 60°C. The measurement was performed until 300°C, and the average value of all the measured values was calculated as CTE. The results are shown in Tables 1 and 2.
[0208]
[0209] <Thickness direction phase difference (Rth) of polyimide film>
[0210] The refractive index nx in the X-axis direction, the refractive index ny in the Y-axis direction, and the refractive index nz in the Z-axis direction of the polyimide films A to U are measured at room temperature (20 to 25°C) and light of a wavelength of 550nm using an optical material inspection device (model RETS-100) manufactured by Otsuka Electronics Co., Ltd. The optical axis is detected, and after phase advance-lag correction, the delay measurement method is measured by a rotation analyzer method. Here, the X-axis and the Y-axis represent the refractive index (nx) in the direction with the largest refractive index in the plane direction of the film, and the refractive index (ny) in the perpendicular direction to the Nx direction in the plane direction of the film, respectively. Then, Rth is calculated from the refractive index nx in the X-axis direction, the refractive index ny in the Y-axis direction, the refractive index nz in the Z-axis direction, and the thickness (d) of the film according to the following formula. The results are shown in Tables 1 and 2.
[0211] Rth(nm)=|[nz-(nx+ny) / 2]×d|
[0212] <Heat shrinkage of polyimide film>
[0213] In the measurement of the coefficient of linear expansion (CTE) of the polyimide film, the film was heated to 300°C and then cooled to 80°C, and the percentage of the ratio of the length of time at 100°C during the initial heating to the length of time at 100°C during the cooling was calculated as the thermal shrinkage. The results are shown in Tables 1 and 2.
[0214] <Interlayer mixing measurement>
[0215] The interlayer intermixing was performed by making an oblique cut surface of the polyimide film using a SAICAS DN-20S model (DAIPLA WINTES). The oblique cut surface was then measured by the microscopic ATR method using a germanium crystal (incident angle 30°) using a microscopic IRCary 620 FTIR (Agilent). Thus, it was confirmed that the intermixing layer of the film other than the film A2 was less than 0.8 μm (800 nm). In addition, the film A2 was 1.5 μm.
[0216]
[0217]
[0218] (Example 1)
[0219] Method for applying silane coupling agent to glass substrate, using Figure 1 The experimental setup shown in was performed. Figure 1 , is a schematic diagram of an experimental device for applying a silane coupling agent to a glass substrate. A glass substrate 1 (OA11G glass (manufactured by NEG) cut to a size of 100 mm × 100 mm and 0.7 mm thick) was used. In addition, the glass substrate 1 was a substrate that was washed with pure water, dried, and then irradiated with a UV / O3 irradiator (SKR1102N-03 manufactured by LAN Technology) for 1 minute for drying. 150 g of 3-aminopropyltrimethoxysilane (silane coupling agent Shin-Etsu Chemical KBM903) was added to a 1L chemical tank, and the outside was heated to 43°C with a water area. The generated steam was then sent into the chamber together with dry air. The gas flow rate was 25 L / min and the substrate temperature was 42°C. The temperature of the dry air was 23°C and the humidity was 1.2% RH. Since the exhaust port was connected to the negative pressure exhaust port, the chamber was confirmed to have a negative pressure of about 10 Pa by a differential pressure gauge. The thickness of the resulting silane coupling agent layer is shown in Table 3.
[0220] Then, a polyimide film A1 (70 mm × 70 mm in size) was attached to the silane coupling agent layer to obtain a laminate, in which the laminated surface was the polyimide surface formed by the polyamic acid solution 3. A laminator manufactured by MCK was used for lamination, and the lamination conditions were: compressed air pressure: 0.6 MPa, temperature: 22°C, humidity: 55% RH, and laminating plate speed: 50 mm / sec. The measurement results of the laminate are shown in Table 3.
[0221] (Example 2)
[0222] A laminate was obtained in the same manner as in Example 1 except that the transparent high heat-resistant film used was changed from Film A1 to Film B. The adhesive surface was the polyimide surface formed from the polyamic acid solution 4. Table 3 shows the measurement results, substrate used, and coating method of the laminate.
[0223] (Example 3)
[0224] A laminate was obtained in the same manner as in Example 1 except that the transparent high heat-resistant film used was changed from Film A1 to Film C. The adhesive surface was the polyimide surface formed from the polyamic acid solution 3. Table 3 shows the measurement results, substrate used, and coating method of the laminate.
[0225] (Example 4)
[0226] A laminate was obtained in the same manner as in Example 1 except that the transparent high heat-resistant film used was changed from Film A1 to Film D1. The adhesive surface was the polyimide surface formed from the polyamic acid solution 3. Table 3 shows the measurement results, substrate used, and coating method of the laminate.
[0227] (Example 5)
[0228] A laminate was obtained in the same manner as in Example 1 except that the transparent high heat-resistant film used was changed from Film A1 to Film D2. The adhesive surface was the polyimide surface formed from the polyamic acid solution 3. Table 3 shows the measurement results, substrate used, and coating method of the laminate.
[0229] (Example 6)
[0230] A laminate is obtained by the same operation as in Example 1 except that the coating method of the silane coupling agent is changed to the following. In the coating method, a glass substrate 1 (OA11G glass (manufactured by NEG) cut to a size of 100 mm × 100 mm and 0.7 mm thick) is placed on a spin coater (MSC-500S, manufactured by JAPAN CREATE). Isopropyl alcohol (IPA) is dripped onto the glass substrate 1, and it is rotated at 500 rpm to spread over the entire surface of the glass substrate. After drying, a 1% IPA solution of silane coupling agent 3-aminopropyltrimethoxysilane (Shin-Etsu Chemical KBM903) is dripped onto the glass, and it is rotated at 2000 rpm to spin dry the diluted silane coupling agent and dry it. Stop the rotation 30 seconds after dripping. Through the above, a silane coupling agent layer is formed on the glass substrate. The measurement results of the laminate are shown in Table 3.
[0231] (Example 7)
[0232] A laminate was obtained in the same manner as in Example 6 except that the transparent high heat-resistant film used was changed from film D2 to film A1. In this case, the adhesive surface was a polyimide surface formed from the polyamic acid solution 3. The measurement results of the laminate are shown in Table 4.
[0233] (Example 8)
[0234] In order to apply SCA, the glass substrate 1 is placed in Example 1. Figure 1 The device is replaced by placing the product formed by fixing the film A1 on the glass substrate 1 with the tape Figure 1 The apparatus was used, and after coating SCA on the film A1, it was peeled off from the glass substrate 1, and the SCA coated surface was brought into contact with the glass side of another glass substrate 1 different from the glass substrate used at this time, and then pasted. The same operation was performed as in Example 1, and a laminate was obtained. In addition, the glass substrate was washed with pure water, dried, and then UV / O 3 The washed substrate was irradiated for 1 minute using an irradiator (SKR1102N-03 manufactured by LAN Technology Co., Ltd.), and then dried. The adhesive surface at this time was the polyimide surface formed by the polyamic acid solution 3. The measurement results of the laminate are shown in Table 4.
[0235] (Example 9)
[0236] In addition to changing the transparent high heat-resistant film used from Film A1 to Film A3 and Figure 1 The same operation as in Example 3 was performed except that the SCA coating time of the device was changed to 5 minutes to obtain a laminate. In this case, the adhesive surface was the polyimide surface formed by the polyamic acid solution 3 coated last. The measurement results of the laminate are shown in Table 4.
[0237] (Example 10)
[0238] A laminate was obtained in the same manner as in Example 5 except that the transparent high heat resistant film used was changed from Film D2 to Film A3. The adhesive surface was the polyimide surface formed from the polyamic acid solution 3 applied last. The evaluation of the obtained laminate is shown in Table 4.
[0239] (Example 11)
[0240] The laminated body was obtained in the same manner as in Example 5 except that the transparent high heat-resistant film used was changed from the film D2 to the film A2. Table 4 shows the evaluation results of the obtained laminated body.
[0241] (Example 12)
[0242] The substrate was changed from glass substrate 1 to glass substrate 2 (730×920 mm). For this purpose, the same operation as in Example 5 was performed except that the application of the silane coupling agent was changed from a laminator to a large-scale device. In this case, the adhesive surface was the polyimide surface formed from the polyamic acid solution 3. The measurement results of the laminate are shown in Table 4.
[0243] (Example 13)
[0244] The laminate was obtained in the same manner as in Example 3 except that the substrate was changed from the glass substrate 1 to a quarter of a silicon wafer (a test piece-grade 8-inch wafer).
[0245] (Example 14)
[0246] The same procedure as in Example 1 was carried out except that the transparent heat-resistant film used was changed to Film M. The surface to which the polyamide solution 6 was applied was used as the bonding surface of the glass substrate.
[0247] (Example 15)
[0248] The same procedure as in Example 1 was carried out except that the transparent heat-resistant film used was changed to Film N. The surface on which the polyamide solution 7 was applied was used as the pasting surface 7 of the glass substrate.
[0249] (Example 16)
[0250] The same procedure as in Example 1 was carried out except that the transparent heat-resistant film used was changed to Film O. The surface on which the polyamide solution 3 was applied was used as the pasting surface 3 of the glass substrate.
[0251] (Example 17)
[0252] The same procedure as in Example 1 was carried out except that the transparent heat-resistant film used was changed to the film P. The surface on which the polyamide solution 3 was applied was used as the pasting surface 3 of the glass substrate.
[0253] (Example 18)
[0254] The same procedure as in Example 1 was carried out except that the transparent heat-resistant film used was changed to Film Q. The surface to which the polyamide solution 3 was applied was used as the bonding surface of the glass substrate.
[0255] (Example 19)
[0256] The same procedure as in Example 1 was carried out except that the transparent heat-resistant film used was changed to Film R. The surface to which the polyamide solution 6 was applied was used as the bonding surface of the glass substrate.
[0257] (Example 20)
[0258] The same procedure as in Example 1 was carried out except that the transparent heat-resistant film used was changed to Film U. The surface to which the polyamide solution 10 was applied was used as the bonding surface of the glass substrate.
[0259] (Circuit production example 1)
[0260] Each of the films obtained above was cut into a roll size of 50 cm wide and subjected to plasma treatment under the following conditions in a continuous vacuum apparatus having a roll unwinding / winding section.
[0261] The plasma treatment conditions were as follows: a frequency of 13.56 MHz, a power of 150 W, a gas pressure of 0.7 Pa, a temperature of 25° C., and a treatment time of 5 minutes in oxygen. Then, a target of a nickel-chromium (15 mass %) alloy was used by RF sputtering in an argon atmosphere at a frequency of 13.56 MHz, a power of 500 W, and a gas pressure of 0.7 Pa. The rate of thickness formation The nickel-chromium alloy film (lower layer) is then Copper is deposited at a rate of 1000 to form a copper film with a thickness of 0.25μm, which is then rolled up in a vacuum. In this way, a single-sided metallized film is formed. On the metal layer side of the film, a nano-laser with a wavelength of 355nm is used to adjust the time to open non-through holes.
[0262] The obtained film with a single-sided metal film and non-through holes is plated using a roll-to-roll longitudinal continuous electroplating device and a copper sulfate plating bath to form a thickened copper plating layer (thickened layer) with a thickness of 3 μm, thereby obtaining the target metallized polyimide film. The obtained metallized polyimide film is cut into pieces with a width of 48 mm and a sprocket hole is formed. After non-electrolytic plating, double-sided through-hole plating is performed in a manner of maximum thickness of 6 μm. Then, the photoresist: FR-200, manufactured by SHIPLEY, is applied and dried, and then exposed in close contact with a glass photomask, and further developed in a 1.2 mass % KOH aqueous solution. Then, an etching solution containing copper chloride of HCl and hydrogen peroxide is used at 40°C and 2 kgf / cm 2 The transparent heat-resistant film with connecting electrodes between the films was produced by etching with a spray pressure of . Thereafter, a laminate with an inorganic substrate was produced in the same manner as in the example.
[0263] (Comparative Example 1)
[0264] A laminate was obtained in the same manner as in Example 1 except that the transparent high heat resistant film used was changed from Film A1 to Film E. The adhesive surface was the polyimide surface that was in contact with the support when the polyamic acid solution was applied. The evaluation of the obtained laminate is shown in Table 6.
[0265] (Comparative Example 2)
[0266] A laminate was obtained in the same manner as in Example 7 except that the transparent high heat resistant film used was changed from Film A1 to Film E. The adhesive surface was the polyimide surface that was in contact with the support when the polyamic acid solution was applied. The evaluation of the obtained laminate is shown in Table 6.
[0267] (Comparative Example 3)
[0268] A laminate was obtained in the same manner as in Example 1 except that the transparent high heat-resistant film used was changed from Film A1 to Film F. The adhesive surface was the polyimide surface that was in contact with the support when the polyamic acid solution was applied. The evaluation of the obtained laminate is shown in Table 6.
[0269] (Comparative Example 4)
[0270] A laminate was obtained in the same manner as in Example 5 except that the transparent high heat-resistant film used was changed from Film A1 to Film G. In this case, the adhesive surface was the polyimide surface formed from the polyamic acid solution 2. Table 6 shows the evaluation results of the obtained laminate.
[0271] (Comparative Example 5)
[0272] A laminate was obtained in the same manner as in Example 5 except that the transparent high heat resistant film used was changed from Film A1 to Film K. The adhesive surface was the polyimide surface that was in contact with the support when the polyamic acid solution was applied. The evaluation of the obtained laminate is shown in Table 6.
[0273] (Comparative Example 6)
[0274] A laminate was obtained in the same manner as in Example 5 except that the transparent high heat-resistant film used was changed from Film A1 to Film L. The adhesive surface was the polyimide surface formed from the polyamic acid solution 3. Table 6 shows the evaluation results of the obtained laminate.
[0275] <Measurement of 90° initial peel strength>
[0276] The laminated body thus prepared was heat treated at 100° C. for 10 minutes in an air atmosphere. Then, the 90° initial peel strength between the inorganic substrate (glass substrate or silicon wafer) and the polyimide film was measured. The results are shown in Tables 2 to 6.
[0277] The measurement conditions of the 90° initial peel strength are as follows.
[0278] The film was peeled off at an angle of 90° with respect to the inorganic substrate.
[0279] The measurement was performed 5 times and the average value was determined.
[0280]
[0281] <Measurement of 90° peel strength after heating at 300°C for 1 hour>
[0282] The laminate obtained by making the above laminate was heat-treated at 100°C for 10 minutes in an air atmosphere. Further, it was heated at 300°C for 1 hour in a nitrogen environment. Then, the 90° peel strength between the inorganic substrate and the polyimide film was measured. The results are shown in Tables 2 to 6. The measurement conditions of the 90° peel strength after heating at 300°C for 1 hour are the same as those of the 90° initial peel strength.
[0283] <Haze of polyimide film>
[0284] The haze of the polyimide film was measured using a haze meter (NDH5000, manufactured by Nippon Denshoku Co., Ltd.). A D65 lamp was used as a light source. The same measurement was performed three times, and the arithmetic mean value was used.
[0285] The results are shown in Tables 2 to 6.
[0286] <Total light transmittance of polyimide film>
[0287] The total light transmittance (TT) of the polyimide film was measured using a haze meter (NDH5000, manufactured by Nippon Denshoku Co., Ltd.). A D65 lamp was used as a light source. The same measurement was performed three times, and the arithmetic mean value was used.
[0288] The results are shown in Tables 2 to 6.
[0289] <Chromaticity of polyimide film>
[0290] Determination of yellow index. Using a colorimeter (ZE6000, manufactured by Nippon Denshoku Co., Ltd.) and C2 light source, the tristimulus values XYZ of the film were measured according to ASTM D1925, and the yellowness index (YI) was calculated according to the following formula. In addition, the same measurement was performed 3 times, and the arithmetic average thereof was adopted.
[0291] YI=100×(1.28X-1.06Z) / Y
[0292] The results are shown in Tables 2 to 6.
[0293] <Warping of a laminate of a transparent high heat-resistant film and an inorganic substrate>
[0294] The warpage (μm) of the laminate of the transparent high heat-resistant film and the inorganic substrate refers to the degree of deformation of the laminate in the thickness direction relative to the plane direction before and after the specific heat treatment described below. Specifically, Figure 4 As shown, a 100 mm × 100 mm test piece is placed on a surface plate in a concave shape at room temperature, and the average value of the distances from the four corners to the plane (h1rt, h2rt, h3rt, h4rt: unit mm) is taken as the original warpage (mm). After heat treatment at 300°C for 1 hour, the test piece is placed on a flat surface in a concave shape, and the average value of the distances from the four corners to the plane (h1, h2, h3, h4: unit mm) is taken as the warpage (mm), and the difference between the average value and the original warpage is taken as the warpage at 300°C. The measured value is the average value of 10 times.
[0295] However, when there are not enough 10 samples, three or more samples are measured. Specifically, the value is calculated according to the following formula.
[0296] Original warpage amount (μm)=(h1rt+h2rt+h3rt+h4rt) / 4
[0297] Warpage (μm) = (h1+h2+h3+h4) / 4
[0298] Warpage at 300°C (μm) = Warpage - Original Warpage
[0299] The results are shown in Tables 2 to 6.
[0300]
Table 3
[0301]
[0302]
Table 4
[0303]
[0304]
Table 5
[0305]
[0306]
Table 6
[0307]
Claims
1. A laminate comprising a transparent high heat-resistant film and an inorganic substrate, which laminate is substantially free of adhesive, The peel strength between the transparent high heat-resistant film and the inorganic substrate is 0.3 N / cm or less in the entire surface, and the CTE of the transparent high heat-resistant film is 50 ppm / K or less. The transparent high heat-resistant film has a laminated structure of two or more layers, and the first transparent high heat-resistant film layer in contact with the inorganic substrate contains a structure of Formula 1 and / or a structure of Formula 2.
2. The laminate according to claim 1, characterized in that The intermixing thickness of the interface between the first transparent high heat-resistant film layer and the second transparent high heat-resistant film layer is less than 800 nm, the first transparent high heat-resistant film layer is in contact with the inorganic substrate, and the second transparent high heat-resistant film layer is not in contact with the inorganic substrate but is adjacent to the first transparent high heat-resistant film layer.
3. The laminate according to claim 1 or 2, characterized in that: The CTE of the first transparent high heat-resistant film layer alone in contact with the inorganic substrate is 20 ppm / K or less.
4. The laminate according to claim 1 or 2, characterized in that: The first transparent high heat-resistant film layer in contact with the inorganic substrate is transparent polyimide.
5. The laminate according to claim 1 or 2, characterized in that: At least one layer of the second transparent high heat-resistant film layer not in contact with the inorganic substrate is a transparent polyimide. 6 . The laminate according to claim 1 , wherein the transparent high heat-resistant film has a total light transmittance of 75% or more. 7 . The laminate according to claim 1 , wherein the total light transmittance of the transparent high heat-resistant film is 75% or more, and the CTE of the first transparent high heat-resistant film layer in contact with the inorganic substrate is 20 ppm / K or less. The laminate according to claim 1 or 2, wherein the yellowness index of the transparent high heat-resistant film is 10 or less. 9 . The laminate according to claim 1 , wherein the yellowness index of the transparent high heat-resistant film is 10 or less, and the CTE of the first transparent high heat-resistant film layer in contact with the inorganic substrate is 20 ppm / K or less. 10 . The laminate according to claim 1 , wherein the laminate structure is a film having a two-layer structure formed of materials having different physical properties.
11. According to the laminated body of claim 1 or 2, the yellowness index of the transparent high heat-resistant film is less than 10, the CTE of the first transparent high heat-resistant film layer in contact with the inorganic substrate is less than 20 ppm / K, and the laminated structure is a two-layer film formed by materials with different physical properties. 12 . The laminate according to claim 1 , wherein a CTE difference between the first transparent high heat-resistant film layer in contact with the inorganic substrate and the second transparent high heat-resistant film layer not in contact with the inorganic substrate is 40 ppm / K or less.
13. According to the laminated body according to claim 1 or 2, the yellowness index of the transparent high heat-resistant film is less than 10, the CTE of the first transparent high heat-resistant film layer in contact with the inorganic substrate is less than 20ppm / K; the CTE difference between the first transparent high heat-resistant film layer in contact with the inorganic substrate and the second transparent high heat-resistant film layer not in contact with the inorganic substrate is less than 40ppm / K; the laminated structure is a film with two layers formed by materials with different physical properties.
14. According to the laminated body according to claim 1 or 2, the yellowness index of the transparent high heat-resistant film is less than 10, and the CTE difference between the first transparent high heat-resistant film layer in contact with the inorganic substrate and the second transparent high heat-resistant film layer not in contact with the inorganic substrate is less than 40ppm / K; the laminated structure is a film with two layers formed by materials with different physical properties. The laminate according to claim 1 or 2, wherein the long side of the inorganic substrate is 300 mm or longer. The laminate according to claim 1 or 2, wherein the peel strength after heat treatment at 300°C or higher for 1 hour in a nitrogen atmosphere is 0.3 N / cm or less.
17. A method for producing a film with an electronic component, comprising forming an electronic component on the transparent high heat-resistant film of the laminate according to any one of claims 1 to 16, and then peeling the film from the inorganic substrate.
Citation Information
Patent Citations
photocell
JP1978004490A
Manufacturing method for display device support substrate polyimide film
JP2018132768A
Alkoxysilane-modified polyamic acid solution, laminate and flexible device using same, polyimide film, and production method for laminate
CN106471065A
Laminate, method for manufacturing the same, and method for manufacturing device structure body using the same
JP2013226784A
Polyimide and method for preparing the same
KR102097431B1